Positive electrode, lithium-air battery including the same, and method for preparing the positive electrode
By using a porous metal oxide film containing lithium as the positive electrode in the lithium-air battery, the problem of radical decomposition during the charging and discharge of the lithium-air battery positive electrode is solved, and more stable battery performance and longer service life are achieved.
Patent Information
- Application Number
- CN202110095391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-04
- Filing Date
- 2021-01-25
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-01-25
AI Technical Summary
The positive electrode of the existing lithium-air battery is prone to decomposition due to the generation of free radicals during charging and discharging, resulting in battery deterioration.
A positive electrode configured to use oxygen as the positive electrode active material is used, the positive electrode includes a porous film containing metal oxides and a surface having a root mean square roughness of about 0.01 micron to about 1 micron and a porosity of about 50% to about 99% by volume.
By using a porous metal oxide film containing lithium as the positive electrode, the positive electrode decomposition caused by free radicals in the electrochemical reaction is suppressed, the charging and discharging characteristics of the lithium-air battery are improved, and the service life of the battery is extended.
Smart Images

Figure CN113224318B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2020-0013301 filed on Feb. 4, 2020 in the Korean Intellectual Property Office and all rights arising therefrom, the contents of which are incorporated herein in their entirety by reference. Technical Field
[0003] The present disclosure relates to a positive electrode, a lithium-air battery including the same, and a method of preparing the positive electrode. Background Art
[0004] The lithium-air battery utilizes lithium itself as the negative electrode, and since there is no need to store air as a positive electrode active material in the battery, a high capacity battery can be realized.
[0005] The theoretical specific energy density of lithium-air batteries is very high, at 3500 watt-hours per kilogram (Wh / kg) or more, which is about ten times the energy density of lithium-ion batteries.
[0006] The positive electrode of commercially available lithium-air batteries is prepared by mixing carbon-based conductive materials, binders and other components. Due to the generation of free radicals involved in the electrochemical reaction during the charging and discharging process of lithium-air batteries, carbon-based conductive materials, binders and other components are easily decomposed.
[0007] Lithium-air batteries that employ a positive electrode that includes a carbon-based conductive material, a binder, and other components are susceptible to degradation.
[0008] A positive electrode that is chemically stable to free radicals generated during the electrochemical reaction is required. Summary of the invention
[0009] Provides a chemically stable positive electrode.
[0010] A lithium-air battery including the positive electrode is provided.
[0011] A method for preparing the positive electrode is provided.
[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description.
[0013] According to one aspect, a positive electrode configured to use oxygen as a positive electrode active material is provided, the positive electrode comprising: a porous membrane, wherein the porous membrane comprises a metal oxide, and wherein a surface of the porous membrane has a root mean square (RMS) roughness (Rq) of about 0.01 micrometers to about 1 micrometer, and the porosity of the porous membrane is about 50 volume % to about 99 volume %, based on the total volume of the porous membrane.
[0014] According to one aspect, a lithium-air battery includes: the positive electrode; a negative electrode including lithium; and an electrolyte disposed between the positive electrode and the negative electrode.
[0015] According to one aspect, a method for preparing a positive electrode includes: providing a composition including a metal oxide and a binder; disposing the composition on a substrate; drying the composition on the substrate to prepare a coating; pressing the coating to prepare a sheet; and heat-treating the sheet at a temperature of about 450 °C to about 800 °C in an oxidizing atmosphere to prepare the positive electrode.
[0016] According to one aspect, a positive electrode configured to use oxygen as a positive electrode active material is disclosed, and the positive electrode includes: a porous membrane, wherein the porous membrane includes a metal oxide, and the metal oxide is a lithium-containing metal oxide represented by Formula 1,
[0017] Formula 1
[0018] Li x A y G z O 3-δ
[0019] wherein, in Formula 1, A and G are each independently at least one element of Group 2 to Group 16, and 0 < x < 1, 0 < y < 1, 0 < x + y ≤ 1, 0 < z ≤ 1.5, and 0 ≤ δ ≤ 1.5, and wherein the surface of the porous membrane has a root mean square roughness of about 0.01 micrometer to about 1 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and other aspects, features, and advantages of some embodiments of the present disclosure will become more apparent from the following description when considered in conjunction with the accompanying drawings, in which:
[0021] Figure 1 is an atomic force microscope (AFM) image of the surface of the positive electrode prepared in Example 1;
[0022] Figure 2 is an AFM image of the surface of the positive electrode prepared in Reference Example 1.
[0023] Figure 3A is a scanning electron microscope image of a cross-section of a dried green sheet before heat treatment prepared in Example 1;
[0024] Figure 3B is a scanning electron microscope image of a cross-section of the positive electrode prepared in Example 1 after heat treatment;
[0025] Figure 4is a graph of voltage (V) versus capacity (milliampere-hour (mAh)), which shows the charge and discharge curves of the lithium-air battery prepared in Example 5;
[0026] Figure 5 is a graph of voltage (V) versus capacity (mAh), which shows the charge and discharge curves of the lithium-air battery prepared in Reference Example 2;
[0027] Figure 6 is a scanning electron microscope image of a cross section of the positive electrode of the lithium-air battery prepared in Example 5 after one discharge cycle;
[0028] Figures 7A to 7C is a schematic diagram showing a positive electrode in the form of a porous film prepared according to the method used in Example 1; and
[0029] Figure 8 is a schematic diagram showing the structure of an embodiment of a lithium-air battery. DETAILED DESCRIPTION
[0030] Embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings, wherein the same reference numerals refer to the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the following only describes the embodiments to illustrate aspects by reference to the accompanying drawings. As used herein, the term "and / or" includes any and all combinations of one or more of the related enumerated items. Expressions such as "at least one (kind)" when before or after a list of elements modify the entire list of elements and do not modify the individual elements of the list.
[0031] The inventive concept described below can be modified in various forms and has many embodiments, and the specific embodiments are illustrated in the drawings and described in detail in the specific embodiments section. However, the inventive concept should not be interpreted as being limited to the specific embodiments, but should be understood to cover all modifications, equivalents or substitutions included in the technical scope of the inventive concept.
[0032] The terms used herein are only used to illustrate the purpose of specific embodiments and are not intended to limit the inventive concept. Singular forms also include plural forms, unless the context clearly indicates otherwise. It will be further understood that the terms "include" or "comprise" when used herein indicate the presence of stated features, values, steps, operations, elements, parts (parts), components, materials, or combinations thereof, but do not exclude the presence or addition of one or more other features, values, steps, operations, elements, parts (parts), components, materials, or combinations thereof. The " / " used hereinafter may be interpreted as "and" or "or" as appropriate.
[0033] In the accompanying drawings, for the sake of clarity, the thickness of layers and regions is enlarged or reduced. The same reference numerals are always designated for similar elements. When a layer, film, region, plate, etc. is referred to as "on" another component, it may be directly on the other component, or there may be an intermediate component. The terms "first", "second", etc. may always be used to describe a variety of elements, but the elements are not limited by the terms. The terms are only used to distinguish an element from another element.
[0034] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of an element to another element as shown in the figure. It will be understood that, in addition to the orientation depicted in the figure, relative terms are also intended to include different orientations of the device. For example, if the device in one of the figures is turned over, the element described as being on the "lower" side of the other element will be oriented on the "upper" side of the other element. Therefore, depending on the specific orientation of the figure, the exemplary term "lower" may include both "lower" and "upper" orientations. Similarly, if the device in one of the figures is turned over, the element described as "below" or "below" the other element will be oriented "above" the other element. Therefore, the exemplary terms "below..." or "below..." may include both "above..." and "below..." orientations.
[0035] As used herein, "about" or "approximately" is inclusive of the stated value and means within an acceptable range of deviation for the particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, 20%, 10%, or 5% relative to the stated value.
[0036] In the present disclosure, the "size" of a pore refers to the average diameter of the pore in the case of spherical pores, or the average length of the major axis of the pore in the case of non-spherical pores. In the present disclosure, a "pore" is an open hole. The average diameter of the pores can be measured, for example, by nitrogen adsorption. Alternatively, the average diameter of the pores can be the arithmetic mean of the pore sizes that can be measured automatically or manually from a scanning electron microscope image, for example, by software.
[0037] In the present disclosure, the "size" of a particle refers to the average diameter of the particle in the case of spherical particles, or the average length of the major axis in the case of non-spherical particles. The average diameter of the particle is the median diameter (D50) of the particle, and is defined by the particle diameter corresponding to the cumulative diameter distribution at 50%, which represents 50% of the particle diameters in the sample. The median diameter (D50) of the particle can be measured using a particle size analyzer (PSA), for example, by light scattering.
[0038] In the present disclosure, “surface roughness” may be measured using an atomic force microscope (AFM).
[0039] The ionic conductivity can be determined by the complex impedance method at 20°C, further details of which can be found in J.-M. Winand et al., "Measurement of Ionic Conductivity in Solid Electrolytes," Europhysics Letters, vol. 8, no. 5, p. 447-452, 1989. In addition, the ionic conductivity can be measured by the DC polarization method as disclosed in Evaluation Method 2.
[0040] As used herein, the term "inorganic material" refers to a material that does not include a carbon-hydrogen bond (CH bond) or a carbon-halogen bond (CX bond, where X is F, Cl, Br or I), or in other words, any material that is not an organic material. For example, carbon fiber is an inorganic material, while a polymer binder or a polymer dispersant is an organic material.
[0041] Spinel compounds are spinel (i.e. MgAl 2 O 4 ) isostructural compounds.
[0042] Perovskite compounds are compounds with perovskite (i.e. CaTiO 3 ) isostructural compounds.
[0043] Layered compounds are compounds with a layered structure, such as a-NaFeO 2 Isostructural compounds such as LiCoO 2 .
[0044] Garnet compounds are compounds with the same structure as garnet (formula X 3 Y 2 (SiO 4 ) 3 Compounds having a crystal structure isomorphous to compounds of the formula (a) wherein X is a divalent cation such as Ca 2+ Mg 2+ , Fe 2+ or Mn 2+ , and Y is a trivalent cation such as Al 3+ , Fe 3+ or Cr 3+ .
[0045] As used herein, NASICON compounds refer to compounds having a crystal structure isostructural with NASICON, which has the chemical formula Na 1+x Zr 2 Si xP 3-x O 12 , where 0 < x < 3.
[0046] As used herein, a LISICON compound refers to a compound having a crystal structure isomorphic to that of LISICON, which has the formula Li 2+2x Zn 1-x GeO 4 , where 0 < x < 1.
[0047] Tavorite is a compound having a crystal structure isomorphic to that of tavorite, and the tavorite is a compound of the formula LiFe(PO 4 )(OH).
[0048] Triplite compound is a compound having a crystal structure isomorphic to that of triplite, and the triplite has the formula (Mn x Fe 1-x ) 2 PO 4 (F y OH 1-y ), where 0 < x < 1 and 0 < y < 1.
[0049] An antiperovskite compound is a compound isomorphic to perovskite (i.e., CaTiO 3 ) except that the anion and cation positions are reversed, such as in Li 3 OBr.
[0050] Silicate refers to a compound including a unit of the formula [SiO (4-2x)- (4-x) , where 0 ≤ x < 2.
[0051] Borate compound refers to a compound including a BO 3 or BO 4 unit, such as Ca 3 (BO 3 ) 2 , or a compound having a crystal structure isomorphic to that of the borate compound.
[0052] "Group" refers to a group of the periodic table according to the 1 - 18 group classification system of the International Union of Pure and Applied Chemistry ("IUPAC").
[0053] Hereinafter, the positive electrode according to an exemplary embodiment, a lithium - air battery including the positive electrode, and a method for preparing the positive electrode will be described in detail.
[0054] According to an embodiment, the positive electrode is configured to use oxygen as a positive electrode active material and includes a porous membrane, wherein the porous membrane includes a metal oxide, and a surface of the porous membrane has a root mean square (RMS) roughness (Rq) of about 0.01 μm to about 1 μm or less, and the porosity of the porous membrane is about 50 volume percent to about 99 volume percent, based on the total volume of the porous membrane.
[0055] The metal oxide included in the positive electrode is structurally and chemically stable. Without being bound by theory, when the positive electrode includes a porous film including a lithium-containing metal oxide, the decomposition of the positive electrode by free radicals involved in the electrochemical reaction is suppressed compared to a positive electrode including a carbon-based conductive material. Therefore, the charge and discharge characteristics of a lithium-air battery including a positive electrode including a porous film including a lithium-containing metal oxide are improved.
[0056] When the porous film included in the commercially available positive electrode has a high surface roughness, there are regions of the film that are not in contact with the current collector, and the discharge products formed in such regions are electrically insulated from the current collector. Therefore, the reversibility of the electrode reaction is deteriorated. As a result, the performance of the lithium-air battery is deteriorated.
[0057] The inventors surprisingly found that when the surface of the porous film included in the positive electrode has an RMS roughness (Rq) of about 1 micrometer (μm) or less, about 0.9 μm or less, about 0.8 μm or less, about 0.7 μm or less, about 0.6 μm or less, about 0.5 μm or less, about 0.4 μm or less, or about 0.3 μm or less, the performance of the lithium-air battery is improved. The RMS roughness (Rq) of the surface of the porous film is, for example, about 0.01 μm to about 1 μm, about 0.02 μm to about 0.9 μm, about 0.03 μm to about 0.8 μm, about 0.04 μm to about 0.7 μm, about 0.05 μm to about 0.6 μm, about 0.06 μm to about 0.5 μm, about 0.07 μm to about 0.4 μm, or about 0.08 μm to about 0.3 μm. When the surface of the porous film has a low surface roughness within such a range, the effective contact area between the current collector and the porous film increases. In addition, when a uniform discharge product is formed on the surface of the porous film during charging and discharging of the lithium-air battery, the electrical insulation of the discharge product and the current collector is limited, and the reversibility of the electrode reaction is improved. As a result, the cycle characteristics of the lithium-air battery are improved.
[0058] The porosity of porous film is, for example, about 50% or higher, about 55% or higher, about 60% or higher, about 65% or higher, about 70% or higher, about 75% or higher, about 80% or higher, about 85% or higher, or about 90% or higher. The porosity of porous film is, for example, about 50% to about 99%, about 51% to about 99%, about 55% to about 99%, about 60% to about 99%, about 65% to about 95%, about 70% to about 95%, about 75% to about 95%, about 80% to about 95%, about 85% to about 95%, or about 90% to about 95%. Porosity is the volume occupied by holes in the gross volume of porous film. When positive electrode includes the porous film with porosity within these ranges, the energy density of battery increases.
[0059] The local porosity of the porous membrane can be changed according to the position in the porous membrane, for example. For example, the porous membrane may include one side and the other side opposite to the one side, and the porosity in the area around the one side may be higher or lower than the porosity in the area around the other side. For example, the porosity in the area around one side of the porous membrane may be about 50% or higher, and the porosity in the area around the other side opposite to the one side may be about 50% or lower. For example, the porosity in the area around one side of the porous membrane may be about 50% to about 99%, and the porosity in the area around the other side opposite to the one side may be about 1% to about 50%. For example, the porous membrane may have a porosity gradient from one side to the other side opposite to the one side. For example, the porous membrane may have a maximum porosity on one side and a minimum porosity on the other side opposite to the one side.
[0060] The average roughness (Ra) of the surface of the porous film is, for example, about 1 μm or less, about 0.9 μm or less, about 0.8 μm or less, about 0.7 μm or less, about 0.6 μm or less, about 0.5 μm or less, about 0.4 μm or less, or about 0.3 μm or less. The average roughness (Ra) of the surface of the porous film is, for example, about 0.01 μm to about 1 μm, about 0.02 μm to about 0.9 μm, about 0.03 μm to about 0.8 μm, about 0.04 μm to about 0.7 μm, about 0.05 μm to about 0.6 μm, about 0.06 μm to about 0.5 μm, about 0.07 μm to about 0.4 μm, or about 0.08 μm to about 0.3 μm. When the surface of the porous film has a low average roughness within these ranges, the effective contact area of the porous film and the current collector increases. In addition, when uniform discharge products are formed on the surface of the porous film during charge and discharge of the lithium-air battery, the electrical insulation of the discharge products and the current collector is limited, and the reversibility of the electrode reaction is improved. As a result, the cycle characteristics of the lithium-air battery are improved.
[0061] The maximum roughness depth (Rmax ) is, for example, about 10 μm or less, about 9 μm or less, about 8 μm or less, about 7 μm or less, about 6 μm or less, about 5 μm or less, about 4 μm or less, or about 3 μm or less. The maximum roughness depth (R max ) is, for example, about 0.1 μm to about 10 μm, about 0.2 μm to about 9 μm, about 0.3 μm to about 8 μm, about 0.4 μm to about 7 μm, about 0.5 μm to about 6 μm, about 0.6 μm to about 5 μm, about 0.7 μm to about 4 μm, or about 0.8 μm to about 3 μm. When the surface of the porous film has a low maximum roughness depth within these ranges, the effective contact area between the porous film and the current collector increases. In addition, when the production of uneven discharge products on the surface of the porous film during charging and discharging of the lithium-air battery is suppressed, the electrical insulation of the discharge products and the current collector is limited, and the reversibility of the electrode reaction is improved. As a result, the cycle characteristics of the lithium-air battery are improved. The RMS roughness (Rq) of the porous film surface, the average roughness (Ra) of the porous film surface, and the maximum roughness depth (R max ) can be measured automatically or manually from AFM images by software.
[0062] The porous film may include, for example, a lithium-containing metal oxide. The lithium-containing metal oxide included in the porous film has lithium ion conductivity and is structurally and chemically stable. When compared to a positive electrode including a carbon-based conductive material, decomposition caused by free radicals generated during an electrochemical reaction of a positive electrode in the form of a porous film including a lithium-containing metal oxide is suppressed. Therefore, the charge and discharge characteristics of a lithium-air battery including such a positive electrode are improved. The lithium-containing metal oxide is an oxide including lithium and one or more metals other than lithium.
[0063] The porous film may have, for example, suitable lithium ion conductivity. The porous film includes a lithium-containing metal oxide and may have lithium ion conductivity.
[0064] The porous membrane may be, for example, an inorganic membrane. The porous inorganic membrane may be composed of, for example, a lithium-containing metal oxide. The porous inorganic membrane may be, for example, a porous membrane that does not include a carbon-based material, for example, a conductive material based on porous carbon. The porous inorganic membrane may be, for example, a porous membrane that does not include an organic component, for example, an organic binder. "Porous inorganic membrane" does not include added organic materials, and is a porous membrane formed substantially using inorganic materials. The porous inorganic membrane may unintentionally (unintentionally) include an organic component, a residue thereof, or a modified product (modification product) thereof used in the preparation process, but the amount of the organic component, the residue thereof, or a modified product thereof may be about 1 weight percent (wt%) or less, about 0.5 weight % or less, about 0.1 weight % or less, about 0.05 weight % or less, about 0.01 weight % or less, or about 0.001 weight % or less, based on the gross weight of the porous inorganic membrane. Alternatively, the porous inorganic membrane may exhibit the following weight change by gasification (evaporation) and / or decomposition of the organic component using thermogravimetric analysis (TGA) at about 25°C to about 900°C: about 1 wt % or less, about 0.5 wt % or less, about 0.1 wt % or less, about 0.05 wt % or less, about 0.01 wt % or less, or about 0.001 wt % or less, based on the initial weight.
[0065] The porous film may be, for example, a self-supporting (free-standing) film. Therefore, the porous film is easy to handle and transport, and can be easily applied to various types of batteries. A self-supporting film refers to a film that maintains a film shape without a supporting layer. The porous film may be a self-supporting film composed of an inorganic metal oxide.
[0066] The porous film includes a large diameter hole, and the size of the large diameter hole is about 1 μm or more. The size of the large diameter hole is about 1 μm to about 100 μm, about 2 μm to about 50 μm, about 3 μm to about 40 μm, about 4 μm to about 30 μm, about 5 μm to about 20 μm, about 5 μm to about 10 μm, or about 5 μm to about 8 μm. When the large diameter hole has a size within these ranges, the excess discharge product obtained with a high discharge capacity may not degrade the positive electrode including the porous film having the large diameter hole. Therefore, a lithium-air battery with high energy density, improved charge and discharge efficiency, and improved cycle characteristics can be obtained.
[0067] The amount of large diameter pores included in the porous film is about 30 volume percent (volume %) or more, about 35 volume % or more, about 40 volume % or more, about 45 volume % or more, or about 50 volume % or more, based on the total volume of the porous film. The amount of large diameter pores included in the porous film is about 30 volume % to about 95 volume %, about 35 volume % to about 90 volume %, about 40 volume % to about 85 volume %, about 45 volume % to about 80 volume %, about 50 volume % to about 75 volume %, about 55 volume % to about 70 volume %, about 55 volume % to about 65 volume %, or about 55 volume % to about 60 volume %, based on the total volume of the porous film. When the porous film has large diameter pores in an amount within these ranges, the storage space of the discharge product increases. Therefore, while maintaining the thickness of the positive electrode in the range of about 5 μm to about 100 μm, the unit cell energy density can be maintained in the range of about 550 watt-hours / kilogram (Wh / kg) to about 650 Wh / kg, for example, about 600 Wh / kg. In addition, when the positive electrode includes a porous membrane, the volume change during charging and discharging of the lithium-air battery can be minimized. In addition, when the positive electrode includes a porous membrane, the diffusion of air or oxygen into the positive electrode is improved.
[0068] The porous membrane may further include a small straight hole, which can be distinguished from a large diameter hole. The size of the small diameter hole included in the porous membrane may be, for example, less than about 1 μm, about 900 nanometers (nm) or less, about 800nm or less, about 700nm or less, about 600nm or less, about 500nm or less, about 400nm or less, about 300nm or less, or about 200nm or less. The size of the small diameter hole included in the porous membrane may be, for example, about 1nm to less than about 1000nm, about 10nm to about 900nm, about 50nm to about 800nm, about 75nm to about 700nm, about 100nm to about 600nm, about 125nm to about 500nm, about 150nm to about 400nm, about 175nm to about 300nm, or about 200nm to about 250nm. When the porous membrane includes such a small diameter hole with a size within these ranges, a high specific surface area can be caused. Therefore, the reaction site area where electrode reactions can occur in an electrode including the porous film can be increased, and as a result, the high rate characteristics of a battery including the porous film can be improved. Small diameter pores include, for example, all pores except large diameter pores.
[0069] The amount of lithium-containing metal oxide included in the porous membrane is about 50 wt % or more, about 60 wt % or more, about 70 wt % or more, about 75 wt % or more, about 80 wt % or more, about 85 wt % or more, about 90 wt % or more, about 95 wt % or more, about 96 wt % or more, about 97 wt % or more, about 98 wt % or more, or about 99 wt % or more, based on the total weight of the porous membrane. The amount of the metal oxide containing lithium included in the porous film is, for example, about 60% by weight to about 100% by weight, about 70% by weight to about 100% by weight, about 75% by weight to about 100% by weight, about 80% by weight to about 100% by weight, about 85% by weight to about 100% by weight, about 90% by weight to about 100% by weight, about 95% by weight to about 100% by weight, about 96% by weight to about 100% by weight, about 97% by weight to about 100% by weight, about 98% by weight to about 100% by weight, or about 99% by weight to about 100% by weight, based on the gross weight of the porous film. When the porous film has the metal oxide content containing lithium within these ranges, a dense and chemically stable positive electrode can be obtained.
[0070] The lithium-containing metal oxide included in the porous film may have a size of about 10 nm to about 500 nm, about 50 nm to about 450 nm, about 100 nm to about 400 nm, about 150 nm to about 350 nm, about 200 nm to about 350 nm, or about 250 nm to about 350 nm.
[0071] The thickness of the porous film may be, for example, about 1 μm to about 1000 μm, about 2 μm to about 500 μm, about 3 μm to about 400 μm, about 4 μm to about 300 μm, about 5 μm to about 200 μm, or about 6 μm to about 100 μm. When the thickness of the porous film is too thin, the mechanical strength may be reduced, and when the thickness of the porous film is too thick, the energy density of the battery may be reduced.
[0072] The loading level of the porous membrane may be, for example, about 4 mg / cm2 (mg / cm 2 ) or higher, about 4.2 mg / cm 2 or higher, about 4.4 mg / cm 2 or higher, about 4.6 mg / cm 2 or higher, about 4.8 mg / cm 2 or higher, about 5 mg / cm 2 or higher, about 5.2 mg / cm 2 or higher, about 5.4 mg / cm 2 or higher, about 5.6 mg / cm 2 or higher, or about 5.8 mg / cm 2 The loading level of the porous membrane may be, for example, about 4 mg / cm2 To about 10mg / cm 2 , about 4.2mg / cm 2 To about 9.5mg / cm 2 , about 4.4mg / cm 2 About 9 mg / cm 2 , about 4.6mg / cm 2 To about 8.5mg / cm 2 , about 4.8mg / cm 2 About 8mg / cm 2 , about 5mg / cm 2 About 8mg / cm 2 , about 5.2mg / cm 2 to about 7.5 mg / cm 2 , about 5.4mg / cm 2 About 7 mg / cm 2 , about 5.6mg / cm 2 About 7 mg / cm 2 , or about 5.8mg / cm 2 About 7 mg / cm 2 When the porous membrane has a loading level within these ranges, the energy density of the battery can be increased. The loading level is the weight of the lithium-containing metal oxide per unit area of the porous membrane.
[0073] The lithium-containing metal oxide included in the porous film is, for example, a crystalline lithium ion conductor. When the lithium-containing metal oxide includes lithium and has crystallinity, the migration path of lithium ions is facilitated. Therefore, the lithium-containing metal oxide is a lithium ion conductor. When the lithium-containing metal oxide is a lithium ion conductor, the positive electrode may not additionally include a separate electrolyte.
[0074] The lithium-containing metal oxide included in the porous film may be, for example, a crystalline electronic conductor. When the lithium-containing metal oxide has crystallinity and electronic conductivity, a migration path for electrons is provided. Therefore, the lithium-containing metal oxide is an electronic conductor. When the lithium-containing metal oxide is an electronic conductor, the positive electrode may not additionally include a separate conductive material.
[0075] The lithium-containing metal oxide included in the porous film may be, for example, a mixed conductor having both lithium ion conductivity and electron conductivity. The mixed conductor may have, for example, a conductivity of about 1×10 -6 Siemens / cm (S / cm) or higher electronic conductivity and about 1×10 -7 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 5×10 -6 S / cm or higher and an electronic conductivity of about 5×10 -7S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 1×10 -5 S / cm or higher and an electronic conductivity of about 1×10 - 6 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 5×10 -5 S / cm or higher and an electronic conductivity of about 5×10 -6 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 1×10 -4 S / cm or higher and an electronic conductivity of about 1×10 -5 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 5×10 -4 S / cm or higher and an electronic conductivity of about 5×10 -5 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 1×10 -3 S / cm or higher and an electronic conductivity of about 1×10 -4 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 5×10 -3 S / cm or higher and an electronic conductivity of about 5×10 -4 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 1×10 -2 S / cm or higher and an electronic conductivity of about 1×10 -3 S / cm or higher ionic conductivity. The mixed conductor has, for example, an ionic conductivity of about 1×10 -1 S / cm or higher and an electronic conductivity of about 1×10 -2 S / cm or higher ion conductivity.
[0076] At a temperature of 25°C, a mixed conductor may have, for example, about 1×10 -6 S / cm is about 1×10 1 S / cm, about 2×10 - 6 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6 S / cm to about 1S / cm, about 1×10 -5S / cm to about 1S / cm, about 2×10 -5 S / cm to about 1S / cm, about 4×10 -5 S / cm to about 1S / cm, about 5×10 -5 S / cm to about 1S / cm, about 1×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm is about 5×10 -1 S / cm, or about 2×10 -4 S / cm is about 1×10 -1 S / cm. At a temperature of 25°C, a mixed conductor may have, for example, about 1×10 -7 S / cm is about 1×10 1 S / cm, about 2×10 -7 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6 S / cm to about 1S / cm, about 1×10 -5 S / cm to about 1S / cm, about 2×10 -5 S / cm to about 1S / cm, about 4×10 -5 S / cm to about 1S / cm, about 5×10 -5 S / cm to about 1S / cm, about 1×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm is about 5×10 -1 S / cm, or about 2×10 -4 S / cm is about 1×10 -1 When the lithium-containing metal oxide provides both ionic conductivity and electronic conductivity as a mixed conductor, a positive electrode can be prepared by using a porous film including the lithium-containing metal oxide without using a separate conductive material and an electrolyte.
[0077] The lithium-containing metal oxide may be, for example, at least one of a spinel compound or a perovskite compound. When the lithium-containing metal oxide includes a compound having such a crystal structure, decomposition of a positive electrode due to free radicals generated in an electrochemical reaction may be suppressed.
[0078] The lithium-containing metal oxides include, for example, perovskite compounds represented by Formula 1:
[0079] Formula 1
[0080] Li x A y G z O 3-δ
[0081] In Formula 1, each A and G is independently at least one element of Group 2 to Group 16, and 0 < x < 1, 0 < y < 1, 0 < x + y ≤ 1, 0 < z ≤ 1.5, and 0 ≤ δ ≤ 1.5. In one aspect, δ represents the oxygen vacancy content.
[0082] The perovskite compound is a compound having a perovskite crystal structure or a perovskite-like crystal structure.
[0083] For example, in Formula 1, A can be at least one of the following: Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, or Er, G can be at least one of the following: Ti, Pd, Pb, Fe, Ir, Co, Rh, Mn, Ni, Cr, Ru, Re, Sn, V, Ge, W, Zr, Mo, Hf, U, Nb, Th, Ta, Bi, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Mg, Al, Si, Sc, Zn, Ga, Rb, Ag, Cd, In, Sb, Pt, Au, or Pb, and 0.2 < x ≤ 0.7, 0 < y ≤ 0.7, 0 < x + y < 1, 0 < z ≤ 1.2, and 0 ≤ δ ≤ 1.2.
[0084] For example, in Formula 1, A can be at least one of the following: La, Ce, Pr, Gd, Ca, Sr, or Ba, M can be at least one of the following: Ti, Mn, Ni, Ru, Cr, Co, Ir, Fe, Pd, Pb, Rh, Sn, V, Re, Ge, W, Zr, Mo, Nb, Ta, Hf, or Bi, and 0.2 < x ≤ 0.5, 0.4 < y ≤ 0.7, 0 < x + y < 1, 0.8 < z ≤ 1.2, and 0 ≤ δ ≤ 1.0.
[0085] The perovskite compound can have, for example, an AB′O 3 phase. Vacancies and lithium (Li) are arranged in some of the A sites of the perovskite structure, and the perovskite compound has a crystalline phase with orthorhombic, cubic, monoclinic, or triclinic symmetry, in which oxygen vacancies exist. Additionally, when the lithium concentration in the A site is optimized, the lithium ion conductivity is excellent, and when a metal (G) with low oxygen vacancy generation energy is introduced into the B site, the electron conductivity is improved.
[0086] Perovskite compounds include, for example, MO 6 Octahedral, six oxygens form MO 6 Vertex in octahedron, wherein M in Formula 1 is located at the center of the octahedron, and the octahedron has corner sharing. The perovskite compound may have a structure in which lanthanum (La), lithium (Li) and vacancies are randomly distributed in a space formed by connection between vertices of the octahedron according to a composition ratio. In the perovskite compound, for example, lithium ions are conducted through the empty layer in lanthanum (La), and electrons are conducted through the metal (G) ion layer.
[0087] According to the results of X-ray diffraction analysis, when analyzed using CuKα radiation, the perovskite compound shows, for example, a main peak at a diffraction angle of 2θ=32.5°±2.5°, and a secondary peak at a diffraction angle (2θ) of 46.5°±2.5° and / or at a diffraction angle (2θ) of 57.5°±2.5°. The main peak refers to a peak with the maximum intensity, and the secondary peak has a weaker intensity than the main peak.
[0088] For example, in the X-ray diffraction of the perovskite compound, the peak intensity at the diffraction angle of 2θ=32.5°±2.5° (I(32.5°±2.5°):I a ) and the peak intensity at the diffraction angle of 2θ = 46.5° ± 2.5° (I(46.5° ± 2.5°):I b ) ratio (I b / I a ) is 0.1 or greater, for example, about 0.1 to about 0.9, for example, about 0.2 to about 0.6. In the X-ray diffraction of the perovskite compound, the peak intensity (I(32.5°±2.5°):I a ) and the peak intensity at the diffraction angle of 2θ = 57.5°±2.5° (I(57.5°±2.5°):I c ) ratio (I c / I a ) is 0.1 or greater, such as from about 0.1 to about 0.9, such as from about 0.2 to about 0.8, such as from about 0.2 to about 0.4.
[0089] The perovskite compound includes, for example, at least one of the following: Li 0.34 La 0.55 TiO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 MnO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 NiO 3-δ (0≤δ≤1.0), Li0.34 La 0.55 CrO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 CoO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 Ir 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 RuO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 FeO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 PdO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 PbO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 RhO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 SnO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 VO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 R 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 GeO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 WO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 ZrO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 MoO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 NbO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 TaO 3-δ (0≤δ≤1.0), Li 0.34 La 0.55 HkDJ 3-δ(0≤δ≤1.0),Li 0.34 Day 0.55 BiO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 TiO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 MnO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 NiO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 CrO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 CO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 IrO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 RuO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 FeO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 PdO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 PbO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 RhO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 SnO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 VO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 ReO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 GeO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 WO 3-δ (0≤δ≤1.0),Li 0.10 Day 0.63 ZrO3-δ (0≤δ≤1.0), Li 0.10 La 0.63 MoO 3-δ (0≤δ≤1.0), Li 0.10 La 0.63 NbO 3-δ (0≤δ≤1.0), Li 0.10 La 0.63 TaO 3-δ (0≤δ≤1.0), Li 0.10 La 0.63 HkDJ 3-δ (0≤δ≤1.0), Li 0.10 La 0.63 BiO 3-δ (0≤δ≤1.0),
[0090] Li 0.20 La 0.60 TiO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 MnO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 NiO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 CrO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 CoO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 Ir 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 RuO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 FeO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 PdO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 PbO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 RhO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 SnO 3-δ (0≤δ≤1.0), Li0.20 La 0.60 VO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 R 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 GeO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 WO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 ZrO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 MoO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 NbO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 TaO 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 HkDJ 3-δ (0≤δ≤1.0), Li 0.20 La 0.60 BiO 3-δ (0≤δ≤1.0),
[0091] Li 0.30 La 0.57 TiO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 MnO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 NiO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 CrO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 CoO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 Ir 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 RuO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57FeO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 PdO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 PbO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 RhO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 SnO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 VO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 R 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 GeO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 WO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 ZrO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 MoO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 NbO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 TaO 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 HkDJ 3-δ (0≤δ≤1.0), Li 0.30 La 0.57 BiO 3-δ (0≤δ≤1.0),
[0092] Li 0.40 La 0.53 TiO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 MnO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 NiO 3-δ(0≤δ≤1.0), Li 0.40 La 0.53 CrO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 CoO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 Ir 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 RuO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 FeO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 PdO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 PbO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 RhO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 SnO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 VO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 R 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 GeO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 WO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 ZrO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 MoO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 NbO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 TaO 3-δ (0≤δ≤1.0), Li 0.40 La 0.53 HkDJ3-δ (0≤δ≤1.0), Li 0.40 La 0.53 BiO 3-δ (0≤δ≤1.0),
[0093] Li 0.45 La 0.52 TiO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 MnO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 NiO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 CrO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 CoO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 Ir 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 RuO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 FeO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 PdO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 PbO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 RhO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 SnO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 VO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 R 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 GeO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 WO 3-δ (0≤δ≤1.0), Li0.45 La 0.52 ZrO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 MoO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 NbO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 TaO 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 HkDJ 3-δ (0≤δ≤1.0), Li 0.45 La 0.52 BiO 3-δ (0≤δ≤1.0),
[0094] Li 0.34 Ce 0.55 TiO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 MnO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 NiO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 CrO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 CoO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 Ir 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 RuO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 FeO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 PdO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 PbO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 RhO 3-δ (0≤δ≤1.0), Li 0.34 Ce0.55 SnO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 VO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 R 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 GeO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 WO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 ZrO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 MoO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 NbO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 TaO 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 HkDJ 3-δ (0≤δ≤1.0), Li 0.34 Ce 0.55 BiO 3-δ (0≤δ≤1.0),
[0095] Li 0.10 Ce 0.63 TiO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 MnO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 NiO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 CrO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 CoO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 Ir 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 RuO 3-δ(0≤δ≤1.0), Li 0.10 Ce 0.63 FeO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 PdO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 PbO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 RhO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 SnO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 VO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 R 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 GeO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 WO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 ZrO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 MoO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 NbO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 TaO 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 HkDJ 3-δ (0≤δ≤1.0), Li 0.10 Ce 0.63 BiO 3-δ (0≤δ≤1.0),
[0096] Li 0.20 Ce 0.60 TiO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 MnO 3-δ (0≤δ≤1.0), Li 0.20Ce 0.60 NiO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 CrO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 CoO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 Ir 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 RuO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 FeO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 PdO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 PbO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 RhO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 SnO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 VO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 R 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 GeO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 WO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 ZrO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 MoO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 NbO 3-δ (0≤δ≤1.0), Li 0.20 Ce 0.60 TaO 3-δ (0≤δ≤1.0), Li0.20 What 0.60 HfO 3-δ (0≤δ≤1.0), Li 0.20 What 0.60 Bio 3-δ (0≤δ≤1.0),
[0097] them 0.30 What 0.57 thio 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 MnO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 NiO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 CrO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 CoO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 IrO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 RuO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 OEM 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 Pd 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 PbO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 RhO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 SnO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 VO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 ReO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57 GeO 3-δ (0≤δ≤1.0), Li 0.30 What 0.57WO 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 ZrO 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 MoO 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 NbO 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 TaO 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 HkDJ 3-δ (0≤δ≤1.0), Li 0.30 Ce 0.57 BiO 3-δ (0≤δ≤1.0),
[0098] Li 0.40 Ce 0.53 TiO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 MnO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 NiO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 CrO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 CoO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 Ir 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 RuO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 FeO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 PdO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 PbO 3-δ (0≤δ≤1.0), Li 0.40 Ce 0.53 RhO 3-δ(0≤δ≤1.0), Li 0.40 Yes 0.53 SnO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 VO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 ReO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 Geo 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 WO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 ZrO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 MoO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 NbO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 Oh my God 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 HfO 3-δ (0≤δ≤1.0), Li 0.40 Yes 0.53 BiO 3-δ (0≤δ≤1.0),
[0099] Li 0.45 Yes 0.52 TiO 3-δ (0≤δ≤1.0), Li 0.45 Yes 0.52 MnO 3-δ (0≤δ≤1.0), Li 0.45 Yes 0.52 NiO 3-δ (0≤δ≤1.0), Li 0.45 Yes 0.52 CrO 3-δ (0≤δ≤1.0), Li 0.45 Yes 0.52 CoO 3-δ (0≤δ≤1.0), Li 0.45 Yes 0.52 IrO 3-δ (0≤δ≤1.0), Li 0.45Ce 0.52 RuO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 FeO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 PdO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 PbO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 RhO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 SnO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 VO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 R 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 GeO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 WO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 ZrO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 MoO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 NbO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 TaO 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 HkDJ 3-δ (0≤δ≤1.0), Li 0.45 Ce 0.52 BiO 3-δ (0≤δ≤1.0),
[0100] Li 0.34 Pr 0.55 TiO 3-δ (0≤δ≤1.0), Li 0.34 Pr 0.55 MnO3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 NiO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 CrO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 CoO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 IrO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 RuO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 FeO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 PdO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 PbO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 RhO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 SnO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 VO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 ReO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 GeO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 W.O. 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 ZrO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 MoO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 NbO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55TaO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 HfO 3-δ (0≤δ≤1.0),Li 0.34 Pr 0.55 BiO 3-δ (0≤δ≤1.0),
[0101] Li 0.10 Pr 0.63 TiO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 MnO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 NiO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 CrO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 CoO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 IrO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 RuO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 FeO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 PdO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 PbO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 RhO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 SnO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 VO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 ReO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 GeO 3-δ(0≤δ≤1.0),Li 0.10 Pr 0.63 W.O. 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 ZrO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 MoO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 NbO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 TaO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 HfO 3-δ (0≤δ≤1.0),Li 0.10 Pr 0.63 BiO 3-δ (0≤δ≤1.0),
[0102] Li 0.20 Pr 0.60 TiO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 MnO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 NiO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 CrO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 CoO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 IrO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 RuO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 FeO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 PdO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 PbO 3-δ (0≤δ≤1.0),Li 0.20Pr 0.60 RhO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 SnO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 VO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 ReO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 GeO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 W.O. 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 ZrO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 MoO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 NbO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 TaO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 HfO 3-δ (0≤δ≤1.0),Li 0.20 Pr 0.60 BiO 3-δ (0≤δ≤1.0),
[0103] Li 0.30 Pr 0.57 TiO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 MnO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 NiO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 CrO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 CoO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 IrO3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 RuO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 FeO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 PdO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 PbO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 RhO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 SnO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 VO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 ReO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 GeO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 W.O. 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 ZrO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 MoO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 NbO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 TaO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 HfO 3-δ (0≤δ≤1.0),Li 0.30 Pr 0.57 BiO 3-δ (0≤δ≤1.0),
[0104] Li 0.40 Pr 0.53 TiO 3-δ (0≤δ≤1.0),Li0.40 Pr 0.53 MnO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 NiO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 CrO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 CoO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 IrO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 RuO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 FeO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 PdO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 PbO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 RhO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 SnO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 VO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 ReO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 GeO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 W.O. 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 ZrO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 MoO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 NbO 3-δ(0≤δ≤1.0),Li 0.40 Pr 0.53 TaO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 HfO 3-δ (0≤δ≤1.0),Li 0.40 Pr 0.53 BiO 3-δ (0≤δ≤1.0),
[0105] Li 0.45 Pr 0.52 TiO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 MnO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 NiO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 CrO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 CoO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 IrO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 RuO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 FeO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 PdO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 PbO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 RhO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 SnO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 VO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 ReO 3-δ (0≤δ≤1.0),Li 0.45Pr 0.52 GeO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 W.O. 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 ZrO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 MoO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 NbO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 TaO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 HfO 3-δ (0≤δ≤1.0),Li 0.45 Pr 0.52 BiO 3-δ (0≤δ≤1.0),
[0106] Li 0.10 Ca 0.80 TiO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 MnO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 NiO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 CrO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 CoO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 IrO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 RuO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 FeO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 PdO 3-δ (0≤δ≤1.0),Li 0.10 Ca 0.80 PbO3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 RhO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 SnO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 VO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 ReO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 Geo 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 WO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 ZrO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 MoO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 NbO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 Oh my God 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 HfO 3-δ (0≤δ≤1.0), Li 0.10 Ca 0.80 BiO 3-δ (0≤δ≤1.0),
[0107] Li 0.20 Ca 0.60 TiO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 MnO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 NiO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 CrO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 CoO 3-δ (0≤δ≤1.0), Li0.20 Ca 0.60 Ir 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 RuO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 FeO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 PdO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 PbO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 RhO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 SnO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 VO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 R 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 GeO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 WO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 ZrO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 MoO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 NbO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 TaO 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 HkDJ 3-δ (0≤δ≤1.0), Li 0.20 Ca 0.60 BiO 3-δ (0≤δ≤1.0),
[0108] Li 0.25 Ca 0.50TiO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 MnO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 NiO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 CrO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 CoO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 Ir 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 RuO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 FeO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 PdO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 PbO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 RhO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 SnO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 VO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 R 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 GeO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 WO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 ZrO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 MoO 3-δ (0≤δ≤1.0), Li 0.25 Ca0.50 NbO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 TaO 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 HkDJ 3-δ (0≤δ≤1.0), Li 0.25 Ca 0.50 BiO 3-δ (0≤δ≤1.0),
[0109] Li 0.30 Ca 0.40 TiO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 MnO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 NiO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 CrO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 CoO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 Ir 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 RuO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 FeO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 PdO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 PbO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 RhO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 SnO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 VO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 R3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 GeO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 WO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 ZrO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 MoO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 NbO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 TaO 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 HkDJ 3-δ (0≤δ≤1.0), Li 0.30 Ca 0.40 BiO 3-δ (0≤δ≤1.0),
[0110] Li 0.40 Ca 0.20 TiO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 MnO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 NiO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 CrO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 CoO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 Ir 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 RuO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 FeO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 PdO 3-δ (0≤δ≤1.0), Li0.40 Ca 0.20 PbO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 RhO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 SnO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 VO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 R 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 GeO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 WO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 ZrO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 MoO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 NbO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 TaO 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 HkDJ 3-δ (0≤δ≤1.0), Li 0.40 Ca 0.20 BiO 3-δ (0≤δ≤1.0),
[0111] Li 0.10 Sr 0.80 TiO 3-δ (0≤δ≤1.0), Li 0.10 Sr 0.80 MnO 3-δ (0≤δ≤1.0), Li 0.10 Sr 0.80 NiO 3-δ (0≤δ≤1.0), Li 0.10 Sr 0.80 CrO 3-δ (0≤δ≤1.0), Li 0.10 Sr 0.80CO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 IrO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 RuO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 FeO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 PdO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 PbO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 RhO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 SnO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 VO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 ReO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 GeO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 WO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 ZrO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 M.O.O 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 NbO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 TaO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 HfO 3-δ (0≤δ≤1.0),Li 0.10 Sr 0.80 BiO 3-δ (0≤δ≤1.0),
[0112] Li 0.20 Sr 0.60 TiO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 MnO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 NiO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 CrO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 CO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 IrO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 RuO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 FeO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 PdO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 PbO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 RhO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 SnO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 VO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 ReO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 GeO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 WO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 ZrO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 M.O.O 3-δ(0≤δ≤1.0),Li 0.20 Sr 0.60 NbO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 TaO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 HfO 3-δ (0≤δ≤1.0),Li 0.20 Sr 0.60 BiO 3-δ (0≤δ≤1.0),
[0113] Li 0.25 Sr 0.50 TiO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 MnO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 NiO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 CrO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 CO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 IrO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 RuO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 FeO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 PdO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 PbO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 RhO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 SnO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 VO 3-δ (0≤δ≤1.0),Li 0.25Sr 0.50 ReO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 GeO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 WO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 ZrO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 M.O.O 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 NbO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 TaO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 HfO 3-δ (0≤δ≤1.0),Li 0.25 Sr 0.50 BiO 3-δ (0≤δ≤1.0),
[0114] Li 0.30 Sr 0.40 TiO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 MnO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 NiO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 CrO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 CO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 IrO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 RuO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 FeO 3-δ (0≤δ≤1.0),Li 0.30 Sr 0.40 PdO3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 PbO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 RhO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 SnO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 VO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 ReO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 GeO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 WO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 ZrO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 MoO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 NbO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 TaO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 HfO 3-δ (0≤δ≤1.0), Li 0.30 Sr 0.40 Bio 3-δ (0≤δ≤1.0),
[0115] Li 0.40 Sr 0.20 TiO 3-δ (0≤δ≤1.0), Li 0.40 Sr 0.20 MnO 3-δ (0≤δ≤1.0), Li 0.40 Sr 0.20 NiO 3-δ (0≤δ≤1.0), Li 0.40 Sr 0.20 CrO 3-δ (0≤δ≤1.0), Li0.40 Sr 0.20 CO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 IrO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 RuO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 FeO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 PdO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 PbO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 RhO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 SnO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 VO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 ReO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 GeO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 WO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 ZrO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 M.O.O 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 NbO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 TaO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 HfO 3-δ (0≤δ≤1.0),Li 0.40 Sr 0.20 BiO 3-δ(0≤δ≤1.0),
[0116] These 0.10 They 0.80 TiO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 MnO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 NiO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 CrO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 CoO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 IrO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 RuO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 FeO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 PdO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 PbO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 RhO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 SnO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 VO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 ReO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 GeO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 WOW 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 ZrO 3-δ (0≤δ≤1.0),Li 0.10They 0.80 MoO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 NbO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 Oh my God 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 HfO 3-δ (0≤δ≤1.0),Li 0.10 They 0.80 Bio 3-δ (0≤δ≤1.0),
[0117] These 0.20 They 0.60 TiO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 MnO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 NiO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 CrO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 CoO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 IrO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 RuO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 FeO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 PdO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 PbO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 RhO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 SnO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 VO3-δ (0≤δ≤1.0),Li 0.20 They 0.60 ReO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 GeO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 WOW 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 ZrO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 MoO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 NbO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 Oh my God 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 HfO 3-δ (0≤δ≤1.0),Li 0.20 They 0.60 Bio 3-δ (0≤δ≤1.0),
[0118] These 0.25 They 0.50 TiO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 MnO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 NiO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 CrO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 CoO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 IrO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 RuO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 FeO 3-δ (0≤δ≤1.0),Li0.25 They 0.50 PdO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 PbO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 RhO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 SnO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 VO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 ReO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 GeO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 WOW 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 ZrO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 MoO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 NbO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 Oh my God 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 HfO 3-δ (0≤δ≤1.0),Li 0.25 They 0.50 Bio 3-δ (0≤δ≤1.0),
[0119] These 0.30 They 0.40 TiO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 MnO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 NiO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40CrO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 CoO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 IrO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 RuO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 FeO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 PdO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 PbO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 RhO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 SnO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 VO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 ReO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 GeO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 WOW 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 ZrO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 MoO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 NbO 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 Oh my God 3-δ (0≤δ≤1.0),Li 0.30 They 0.40 HfO 3-δ (0≤δ≤1.0),Li 0.30 They0.40 Bio 3-δ (0≤δ≤1.0),
[0120] These 0.40 They 0.20 TiO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 MnO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 NiO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 CrO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 CoO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 IrO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 RuO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 FeO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 PdO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 PbO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 RhO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 SnO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 VO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 ReO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 GeO 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 WOW 3-δ (0≤δ≤1.0),Li 0.40 They 0.20 ZrO 3-δ(0≤δ≤1.0), Li 0.40 Ba 0.20 MoO 3-δ (0≤δ≤1.0), Li 0.40 Ba 0.20 NbO 3-δ (0≤δ≤1.0), Li 0.40 Ba 0.20 TaO 3-δ (0≤δ≤1.0), Li 0.40 Ba 0.20 HkDJ 3-δ (0≤δ≤1.0), Li 0.40 Ba 0.20 BiO 3-δ (0≤δ≤1.0),
[0121] Li 0.25 La 0.50 TiO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 MnO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 NiO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 CrO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 CoO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 Ir 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 RuO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 FeO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 PdO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 PbO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 RhO 3-δ (0≤δ≤1.0), Li 0.25 La 0.50 SnO 3-δ (0≤δ≤1.0), Li 0.25Day 0.50 VO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 ReO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 GeO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 WO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 ZrO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 M.O.O 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 NbO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 TaO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 HfO 3-δ (0≤δ≤1.0),Li 0.25 Day 0.50 BiO 3-δ (0≤δ≤1.0),
[0122] Li 0.05 Day 0.82 Tea 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 Mr 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 Mr 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day 0.77 Mr 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 No 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 No 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day0.77 No 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 Dad 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 Dad 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day 0.77 Dad 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 V 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 V 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day 0.77 V 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 W 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 W 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day 0.77 W 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 Mo 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 Mo 0.70 O 3-δ (0≤δ≤1.0),Li 0.20 Day 0.77 Mo 0.70 O 3-δ (0≤δ≤1.0),Li 0.05 Day 0.82 Bi 0.70 O 3-δ (0≤δ≤1.0),Li 0.10 Day 0.80 Bi 0.70 O 3-δ(0≤δ≤1.0), Li 0.20 La 0.77 Bi 0.70 O 3-δ (0≤δ≤1.0), Li 0.05 La 0.82 Cr 0.70 O 3-δ (0≤δ≤1.0), Li 0.10 La 0.80 Cr 0.70 O 3-δ (0≤δ≤1.0), or Li 0.20 La 0.77 Cr 0.70 O 3-δ (0≤δ≤1.0).
[0123] The perovskite compound is, for example, Li 0.31 La 0.56 TiO 3 , Li 0.34 La 0.55 RuO 3 , Li 0.2 Ca 0.6 Mn 0.5 Ni 0.5 O 3 , Li 0.34 La 0.55 RuO 3-δ or Li 0.2 Ca 0.6 Mn 0.5 Ni 0.5 O 3-δ , but not limited thereto, and any suitable compound providing both electron conductivity and ion conductivity may be used as the lithium-containing perovskite compound.
[0124] The perovskite compound has, for example, a carbon monoxide content of about 1×10 -6 S / cm or higher and an electronic conductivity of about 1×10 -7 S / cm or higher ion conductivity.
[0125] The electronic conductivity of the perovskite compound at 25° C. is, for example, about 5×10 -6 S / cm or higher, about 1×10 -5 S / cm or higher, about 5×10 -5 S / cm or higher, about 1×10 -4 S / cm or higher, about 5×10 -4 S / cm or higher, about 1×10 -3 S / cm or higher, about 5×10 -3S / cm or higher, about 1×10 -2 S / cm or higher, about 5×10 -2 S / cm or higher, or about 1×10 -1 S / cm or more. At a temperature of 25°C, the perovskite compound may have, for example, about 1×10 -6 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6 S / cm to about 1S / cm, about 1×10 -5 S / cm to about 1S / cm, about 2×10 -5 S / cm to about 1S / cm, about 4×10 -5 S / cm to about 1S / cm, about 5×10 -5 S / cm to about 1S / cm, about 1×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm is about 5×10 -1 S / cm, or about 2×10 -4 S / cm is about 1×10 -1 When the perovskite compound has an electronic conductivity within these ranges, the internal resistance of a positive electrode and a battery including the perovskite compound is reduced. As a result, the cycle characteristics of the battery are improved.
[0126] The ionic conductivity of the perovskite compound at 25° C. is, for example, about 5×10 -7 S / cm or higher, about 1×10 -6 S / cm or higher, about 5×10 -6 S / cm or higher, about 1×10 -5 S / cm or higher, about 5×10 -5 S / cm or higher, about 1×10 -4 S / cm or higher, about 5×10 -4 S / cm or higher, about 1×10 -3 S / cm or higher, about 5×10 -3 S / cm or higher, or about 1×10 -2 S / cm or more. At a temperature of 25°C, the perovskite compound may have, for example, about 1×10-7 S / cm to about 1×10 1 S / cm, about 2×10 -7 S / cm to about 1×10 1 S / cm, about 2×10 -6 S / cm to about 5 S / cm, about 4×10 -6 S / cm to about 5 S / cm, about 4×10 -6 S / cm to about 1 S / cm, about 5×10 -6 S / cm to about 1 S / cm, about 1×10 -5 S / cm to about 1 S / cm, about 2×10 -5 S / cm to about 1 S / cm, about 4×10 -5 S / cm to about 1 S / cm, about 5×10 -5 S / cm to about 1 S / cm, about 1×10 -4 S / cm to about 1 S / cm, about 2×10 -4 S / cm to about 1 S / cm, about 2×10 -4 S / cm to about 5×10 -1 S / cm, or about 2×10 -4 S / cm to about 1×10 -1 S / cm of ionic conductivity. When the perovskite compound has an ionic conductivity within these ranges, the internal resistance of the positive electrode and the battery including the perovskite compound is reduced. As a result, the cycle characteristics of the battery are improved.
[0127] The lithium-containing metal oxide includes, for example, a spinel compound represented by Formula 2 or Formula 3:
[0128] Formula 2
[0129] Li 1±x M 2±y O 4-δ1
[0130] Formula 3
[0131] Li 4±a M 5±b O 12-δ2
[0132] In Formulas 2 and 3, each M is independently at least one element of Groups 2 to 16, and 0 < x < 1, 0 < y < 1, 0 ≤ δ1 ≤ 1, 0 < a < 2, 0.3 < b < 5, and 0 ≤ δ2 ≤ 3. In one aspect, δ1 and δ2 may represent oxygen vacancies.
[0133] The spinel compound is a compound having a spinel crystal structure or a spinel-like crystal structure.
[0134] For example, in Formulas 2 and 3, each M can independently be at least one of the following: Ni, Pd, Pb, Fe, Ir, Co, Rh, Mn, Cr, Ru, Re, Sn, V, Ge, W, Zr, Ti, Mo, Hf, U, Nb, Th, Ta, Bi, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Mg, Al, Si, Sc, Zn, Ga, Rb, Ag, Cd, In, Sb, Pt, Au, or Pb, and 0 < x < 1, 0 < y < 1, 0 ≤ δ1 ≤ 1, 0 < a < 2, 0.3 < b < 5, and 0 ≤ δ2 ≤ 3.
[0135] The spinel compound can be represented, for example, by Formula 4:
[0136] Formula 4
[0137] Li 4±a Ti 5-b M' c O 12-δ
[0138] In Formula 4, M' is at least one of the following: Cr, Mg, Ca, Sr, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Hf, V, Nb, Ta, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, Bi, Po, As, Se, or Te, and 0.3 < a < 2, 0.3 < b < 2, 0.3 < c < 2, and 0 ≤ δ ≤ 3. For example, 0 ≤ δ ≤ 2.5, 0 ≤ δ ≤ 2, 0 ≤ δ ≤ 1.5, 0 ≤ δ ≤ 1, and 0 ≤ δ ≤ 0.5.
[0139] The spinel compound of Formula 4 has, for example, a peak intensity ratio (Ia / Ib) of the peak intensity (Ia) of the (111) crystal plane at a diffraction angle of 2θ = 18° ± 2.5° to the peak intensity (Ib) at a diffraction angle of 2θ = 23.5° ± 2.5° in the XRD spectrum as follows: about 1 or less, about 0.9 or less, about 0.8 or less, about 0.7 or less, about 0.6 or less, about 0.5 or less, or about 0.4 or less. When the spinel compound has the above peak intensity ratio, the electron conductivity and ion conductivity are further improved.
[0140] The spinel compound of Formula 4 includes, for example, another phase in addition to the phase having the spinel-like crystal structure. For example, the composite conductor (spinel compound of Formula 4) includes a phase having a spinel-like crystal structure of the term Fd-3m space group, and further includes one or more other phases different from the phase having the spinel-like crystal structure, which are at least one of the following: Li 2 TiO 3 , Gd 2 Ti 2 O 7 、GdTiO 3 、LiNbO 3 or Nb 2 O 5 When the composite conductor has a polycrystalline structure including such a plurality of different phases, electronic conductivity and ionic conductivity are further improved.
[0141] The band gap between the valence band and the conduction band of the spinel compound of Formula 4 is, for example, about 2 eV or less, about 1.8 eV or less, about 1.6 eV or less, about 1.4 eV or less, or about 1.2 eV or less, for example, about 0.1 eV to about 2 eV, or about 0.5 eV to about 1.8 eV. When the band gap between the valence band and the conduction band of the composite conductor is below these limits, electrons easily migrate from the valence band to the conduction band, and therefore, the electronic conductivity of the spinel compound is improved.
[0142] In the spinel compound of Formula 4, Ti has one or more oxidation numbers selected from, for example, trivalent or tetravalent. For example, when Ti has a mixed valence state (through which a plurality of oxidation numbers different from each other exist in the composite conductor), a new state density function is added near the Fermi energy (Ef), and the band gap between the valence band and the conduction band is reduced. As a result, the electronic conductivity of the spinel compound is improved.
[0143] In the spinel compound of Formula 4, M' has an oxidation number different from, for example, at least one oxidation number of Ti. For example, when M' having an oxidation number different from that of Ti is additionally included in the composite conductor, a new state density function is added near the Fermi energy (Ef), and the band gap between the valence band and the conduction band is reduced. As a result, the electronic conductivity of the spinel compound is even further improved.
[0144] When oxygen vacancies are included in the spinel compound of Formula 4, improved ionic conductivity can be provided. In addition, when the composite conductor includes oxygen vacancies, the position of the state density function shifts to the vicinity of the Fermi energy (Ef), and the band gap between the valence band and the conduction band decreases. As a result, the electronic conductivity of the spinel compound is improved.
[0145] The spinel compound includes, for example, at least one of the following: Li 4±xOf 5-y Mg z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Ca z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Mr. z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Sc z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y La z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Pr z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Sm z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Eu z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±xOf 5-y Good z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Dy z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Hoo z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Er z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Tm z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Hit z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Zr z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Hf z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y V z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±xOf 5-y Nb z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Sell z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Know z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y W z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Mn z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Tc z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Soak z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Want z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Ru z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Oh. z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Co z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±xOf 5-y Rh z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Ir z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y In z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Pd z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Pt. z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Cu z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Ag z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Oh, oh z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Zn z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y CD z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Hg z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±xOf 5-y Al z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Tall z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y In z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Yes z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Cut z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Sn z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Pb z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Sb z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Like z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y Too much z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±x Of 5-y As z SHE 12-δ (0.4 <x≤1,0.4<y≤1,0.4<z≤1,0<δ≤3),Li 4±xTi 5-y Se z O 12-δ (0.4 < x ≤ 1, 0.4 < y ≤ 1, 0.4 < z ≤ 1, 0 < δ ≤ 3), or Li 4±x Ti 5-y Te z O 12-δ (0.4 < x ≤ 1, 0.4 < y ≤ 1, 0.4 < z ≤ 1, 0 < δ ≤ 3).
[0146] The spinel compound is, for example, LiMn 2 O 4 、LiTiNbO 4 、Li 4 Ti 5 O 12 、Li 4 Mn 5 O 12 或Li 4.5 Ti 4.5 Gd 0.5 O 12 , but not limited thereto, and any suitable lithium-containing compound that acts as a spinel compound and provides both electronic conductivity and ionic conductivity can be used.
[0147] The spinel compound has, for example, an electronic conductivity of about 1×10 -6 S / cm or higher and an ionic conductivity of about 1×10 -7 S / cm or higher at 25°C.
[0148] The electronic conductivity of the spinel compound at 25°C is, for example, about 5×10 -6 S / cm or higher, about 1×10 -5 S / cm or higher, about 5×10 -5 S / cm or higher, about 1×10 -4 S / cm or higher, about 5×10 -4 S / cm or higher, about 1×10 -3 S / cm or higher, about 5×10 -3 S / cm or higher, about 1×10 -2 S / cm or higher, about 5×10 -2 S / cm or higher, or about 1×10 -1 S / cm or higher. At a temperature of 25°C, the spinel compound can have, for example, about 1×10 -6 S / cm to about 1×10 1 S / cm, about 2×10 -6 S / cm to about 1×10 1 S / cm, about 2×10-6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6 S / cm to about 1S / cm, about 1×10 -5 S / cm to about 1S / cm, about 2×10 -5 S / cm to about 1S / cm, about 4×10 -5 S / cm to about 1S / cm, about 5×10 -5 S / cm to about 1S / cm, about 1×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm is about 5×10 -1 S / cm, or about 2×10 -4 S / cm is about 1×10 -1 When the spinel compound has an electronic conductivity within these ranges, the internal resistance of a positive electrode and a battery including the spinel compound is reduced. As a result, the cycle characteristics of the battery are improved.
[0149] The ionic conductivity of the spinel compound at 25° C. is, for example, about 5×10 -7 S / cm or higher, about 1×10 -6 S / cm or higher, about 5×10 -6 S / cm or higher, about 1×10 -5 S / cm or higher, about 5×10 -5 S / cm or higher, about 1×10 -4 S / cm or higher, about 5×10 -4 S / cm or higher, about 1×10 -3 S / cm or higher, about 5×10 -3 S / cm or higher, or about 1×10 -2 S / cm or more. At a temperature of 25°C, the spinel compound may have, for example, about 1×10 -7 S / cm is about 1×10 1 S / cm, about 2×10 -7 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6from about 1×10 -5 S / cm to about 1 S / cm, about 2×10 -5 S / cm to about 1 S / cm, about 4×10 -5 S / cm to about 1 S / cm, about 5×10 -5 S / cm to about 1 S / cm, about 1×10 -4 S / cm to about 1 S / cm, about 2×10 -4 S / cm to about 1 S / cm, about 2×10 -4 S / cm to about 5×10 -1 S / cm, or about 2×10 -4 S / cm to about 1×10 -1 S / cm of ionic conductivity. When the spinel compound has an ionic conductivity within these ranges, the internal resistance of the positive electrode and the battery including the spinel compound is reduced. As a result, the cycle characteristics of the battery are improved.
[0150] In addition, the lithium-containing metal oxide may include at least one of the following: a layered compound, a garnet compound, a NASICON compound, a LISICON compound, a phosphate compound, a lithiophilite compound, a triphylite compound, an inverse perovskite compound, a silicate compound, or a borate compound. When the lithium-containing metal oxide includes a compound having such a crystal structure, the decomposition of the positive electrode caused by radicals involved in the electrochemical reaction is suppressed.
[0151] The lithium-containing metal oxide may include, for example, a layered compound represented by Formula 5:
[0152] Formula 5
[0153] Li 1±x M 1±y O 2±δ
[0154] In Formula 5, M in Formula 5 is at least one element of Groups 2 to 16, and 0 < x < 0.5, 0 < y < 1, and 0 ≤ δ ≤ 1.
[0155] The layered compound is a compound having a layered crystal structure.
[0156] The layered compound is a compound represented by, for example, at least one of the following: Li a A 1-b B′ b D 2 (where 0.90 ≤ a ≤ 1.8 and 0 ≤ b ≤ 0.5); Li a E 1-b B′ b O 2-c Dc (where 0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); LiE 2-b B′ b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B′ c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Co b B′ c O 2-α F′ α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b B′ c O 2-α F′ 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B′ c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b- c Mn b B′ c O 2-α F′ α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B′ c O 2-α F′ 2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li a Nib Co c Mn d G e O 2 (where 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5 and 0.001 ≤ e ≤ 0.1); Li a NiG b O 2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); Li a CoG b O 2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); and Li a MnG b O 2 (where 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1).
[0157] A is at least one of the following: Ni, Co or Mn; B' is at least one of the following: Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V or rare earth elements; D is at least one of the following: O, F, S or P; E is at least one of the following: Co or Mn; F' is at least one of the following: F, S or P; G is at least one of the following: Al, Cr, Mn, Fe, Mg, La, Ce, Sr or V.
[0158] The layered compound is, for example, LiNiO 2 , LiCoO 2 , LiMnO 2 , LiNi 1-x Mn x O 2 (0 < x < 1), LiNi 1-x- y Co x Mn y O 2 (0 < x ≤ 0.5, 0 < y ≤ 0.5), LiNi 0.8 Co 0.1 Mn 0.1 O 2 , or LiNi 1-x-y Co x Al y O 2 (0 < x ≤ 0.5, 0 < y ≤ 0.5), but is not limited thereto, and any suitable compound that can be used as a lithium-containing layered compound can be used.
[0159] The lithium-containing metal compound may include, for example, a NASICON compound represented by Formula 6:
[0160] Formula 6
[0161] Li 1+x A x M 2-x (XO 4 )
[0162] In Formula 6, each A and M in Formula 6 are each independently at least one element of Group 2 to Group 16, X is As, P, Mo or S, and 0 < x < 1.0.
[0163] The NASICON compound is a compound having a NASICON crystal structure, such as a compound isostructural with NASICON.
[0164] The NASICON compound is, for example, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 、Li 1.3 Al 0.3 Ge 1.7 (PO 4 ) 3 或Li 1.3 Al 0.3 Zr 1.7 (PO 4 ) 3 , but not limited thereto, any suitable lithium-containing NASICON compound can be used.
[0165] The lithium-containing metal oxide may include, for example, the LISICON compound represented by Formula 7:
[0166] Formula 7
[0167] Li 8-c A a B′ b O 4
[0168] In Formula 7, each A and B′ in Formula 7 are each independently at least one element of Group 2 to Group 16, c = ma + nb, where m is the oxidation number of A, n is the oxidation number of B', and 0 < a ≤ 1 and 0 ≤ b ≤ 1.
[0169] The LISICON compound is a compound having a LISICON crystal structure or a LISICON-like crystal structure.
[0170] The LISICON compound is, for example, Li 4 SiO 4 、Li 3.75 Si 0.75 P 0.25 O4 , Li 14 Zn(GeO 4 ) 4 , Li 3.4 V 0.6 Ge 0.4 O 4 , or Li 3.5 V 0.5 Ti 0.5 O 4 , but not limited thereto, any suitable lithium-containing LISICON compound may be used.
[0171] The lithium-containing metal oxide may include, for example, a garnet compound represented by Formula 8:
[0172] Formula 8
[0173] Li x A 3 B′ 2 O 12
[0174] In Formula 8, each of A and B′ in Formula 8 is independently at least one of Group 2 to Group 16 elements, and 3.0≤x≤7.0.
[0175] The garnet compound is a compound having a garnet crystal structure or a garnet-like crystal structure.
[0176] The garnet compound is, for example, Li 3 Tb 3 Te 2 O 12 , Li 4.22 Al 0.26 La 3 Zr 2 WO 12 , Li 5 La 3 Nb 2 O 12 , Li 6 BaLa 2 Ta 2 O 12 , or Li 7 La 3 Zr 2 O 12 , but not limited thereto, any suitable lithium-containing garnet compound may be used.
[0177] The lithium-containing metal oxide may include, for example, a phosphate compound represented by Formula 9 or Formula 10:
[0178] Formula 9
[0179] Li1±x MPO 4
[0180] Formula 10
[0181] Li 2 MP 2 O 7
[0182] In Formulae 9 and 10, each M in Formulae 9 and 10 is independently at least one of Group 2 to Group 16 elements, and 0≤x≤1.0.
[0183] The compound represented by Formula 9 is an olivine compound. The olivine compound is a compound having an olivine crystal structure or an olivine-like crystal structure.
[0184] The phosphate compound is, for example, LiFePO 4 、LiMnPO 4、 LiCoPO 4 、LiNiPO 4 , Li 2 MnP 2 O 7 , or Li 2 FeP 2 O 7 , but not limited thereto, any suitable lithium-containing phosphate compound may be used.
[0185] The lithium-containing metal oxide may include, for example, a ferroxenite compound or a ferroxenite compound represented by Formula 11:
[0186] Formula 11
[0187] Li 1±x M(TO 4 )X′
[0188] In Formula 11, M in Formula 11 is at least one of Group 2 to Group 16 elements, T is P or S, X′ is F, O or OH, and 0≤x≤1.0.
[0189] The ferroxite compound is a compound having a ferroxite crystal structure or a ferroxite-like crystal structure. The ferroxite compound is a compound having a ferroxite crystal structure or a ferroxite-like crystal structure.
[0190] The hydroxyapatite compound or fluoroapatite compound is, for example, LiVO(PO 4 )、LiV(PO 4 )F、LiFe(SO 4 )F, or Li 2 Fe(PO 4)F, but not limited thereto, and any suitable lithium-containing ferroxenite compound or ferroxenite compound may be used. The ferroxenite compound and ferroxenite compound have the same composition but different crystal structures.
[0191] The lithium-containing metal oxide may include, for example, an antiperovskite compound represented by Formula 12:
[0192] Formula 12
[0193] Li x M y OA
[0194] In Formula 12, M in Formula 12 is at least one of Group 2 to Group 16 elements, A is F, Cl, Br, I, S, Se, or Te, and 2.0≤x≤3.0 and 0≤y≤1.0.
[0195] The antiperovskite compound has a perovskite crystal structure or a perovskite-like crystal structure, but is a compound in which the positions of cations and anions are exchanged oppositely to those of the perovskite compound.
[0196] The antiperovskite compound is, for example, Li 3 OCl、Li 2 OHBr、Li 2 (OH) 0.9 F 0.1 Cl, or Li 3 OCl 0.5 Br 0.5 , but not limited thereto, and any suitable compound serving as a lithium-containing antiperovskite compound may be used.
[0197] The lithium-containing metal oxide may include, for example, at least one silicate compound represented by Formula 13:
[0198] Formula 13
[0199] Li 2±x MSiO 4
[0200] In Formula 13, M in Formula 13 is at least one of Group 2 to Group 16 elements, and 0≤x≤1.0.
[0201] The silicate compound may include SiO 4 4- Crystalline compounds of anions.
[0202] The silicate compound is, for example, Li 2 MnSiO 4 or Li 2 FeSiO 4, but not limited thereto, and any suitable lithium-containing silicate compound may be used.
[0203] The lithium-containing metal oxide may include, for example, at least one borate compound represented by Formula 14:
[0204] Formula 14
[0205] Li 1±x MBO 3
[0206] In Formula 14, M in Formula 14 is at least one of Group 2 to Group 16 elements, and 0≤x≤1.0.
[0207] The borate compound may include BO 3 3- Crystalline compounds of anions.
[0208] The borate compound is, for example, LiFeBO 3 or LiCoBO 3 , but not limited thereto, and any suitable lithium-containing borate compound may be used.
[0209] The electron conductivity at 25° C. of the layered compound represented by Formula 5, the NASICON compound represented by Formula 6, the LISICON compound represented by Formula 7, the garnet compound represented by Formula 8, the phosphate compound represented by at least one of Formula 9 or Formula 10, the hydroxyapatite compound or the fluoroapatite compound represented by Formula 11, the antiperovskite compound represented by Formula 12, the silicate compound represented by Formula 13, or the borate compound represented by Formula 14 is, for example, about 1×10 - 6 S / cm or higher, about 5×10 -6 S / cm or higher, about 1×10 -5 S / cm or higher, about 5×10 -5 S / cm or higher, about 1×10 -4 S / cm or higher, about 5×10 -4 S / cm or higher, about 1×10 -3 S / cm or higher, about 5×10 -3 S / cm or higher, about 1×10 -2 S / cm or higher, about 5×10 -2 S / cm or higher, or about 1×10 -1 S / cm or higher. The ionic conductivity may be about 1×10 -6 S / cm is about 1×10 1 S / cm, about 2×10 -6 S / cm is about 1×10 1S / cm, about 2×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 5S / cm, about 4×10 -6 S / cm to about 1S / cm, about 5×10 -6 S / cm to about 1S / cm, about 1×10 -5 S / cm to about 1S / cm, about 2×10 -5 S / cm to about 1S / cm, about 4×10 -5 S / cm to about 1S / cm, about 5×10 -5 S / cm to about 1S / cm, about 1×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm to about 1S / cm, about 2×10 -4 S / cm is about 5×10 -1 S / cm, or about 2×10 -4 S / cm is about 1×10 -1 When the compounds of Formulae 5 to 14 have ionic conductivity within these ranges, the internal resistance of a positive electrode and a lithium-air battery including the compounds of Formulae 5 to 14 is reduced.
[0210] In addition to the lithium-containing metal oxide, the porous membrane may include an additional electron conductor. When the additional electron conductor is included, the electron conductivity of the porous membrane increases.
[0211] The porous membrane may include, for example, an electron conductor represented by Formula 15 or Formula 16.
[0212] Formula 15
[0213] A x B′ y O 3±δ
[0214] In Formula 15, each of A and B′ in Formula 15 is independently at least one of Group 2 to Group 16 elements, and 0.8≤x≤1.2, 0.8≤y≤1.2, and 0≤δ≤1.5.
[0215] Formula 16
[0216] Ce x M y O 3±δ
[0217] In Formula 16, M in Formula 16 is at least one of Group 2 to Group 16 elements, and 0.6≤x≤1.0, 0≤y≤0.4, and 0≤δ≤0.5.
[0218] For example, in Formula 15, A is at least one of Sr, Ba, or La, and B′ is at least one of Zr, Ce, Sc, Y, In, or Yb.
[0219] For example, in Formula 16, M in Formula 16 is at least one of the following: Sc, Y, Zr, In, La, Pr, Sm, Gd, or Yb.
[0220] The porous membrane may include, for example, an electronic conductor such as LaRuO 3 .
[0221] The lithium-containing metal oxide included in the porous film is electrochemically stable relative to lithium metal, for example, in a voltage range of about 2.0 volts (V) to about 4.0 V. Therefore, the porous film can be used for a long time in a battery having an operating voltage of about 2.0 V to about 4.0 V relative to lithium metal.
[0222] A lithium-air battery according to an embodiment includes: the above-described positive electrode; a negative electrode including lithium; and an electrolyte provided between the positive electrode and the negative electrode.
[0223] When a lithium-air battery uses a positive electrode having a porosity of about 50% or more and a surface RMS roughness (Rq) of about 1 μm or less and in the form of a porous film including a lithium-containing metal oxide, the structural stability of the lithium-air battery is improved, its degradation is suppressed, and its cycle characteristics are improved.
[0224] The lithium-air battery includes a positive electrode. The positive electrode is an air electrode. The positive electrode is, for example, located on a positive electrode current collector.
[0225] The positive electrode adopts a porous film including the metal oxide containing lithium. Based on 100 parts by weight of the positive electrode, the amount of the metal oxide containing lithium is, for example, about 1 part by weight to about 100 parts by weight, about 10 parts by weight to about 99 parts by weight, about 50 parts by weight to about 98 parts by weight, about 60 parts by weight to about 97 parts by weight, about 70 parts by weight to about 96 parts by weight, about 80 parts by weight to about 95 parts by weight, or about 90 parts by weight to about 95 parts by weight. The positive electrode is, for example, substantially composed of a porous film. Moreover, the porous film is, for example, substantially composed of a metal oxide containing lithium. Because the positive electrode is substantially composed of a porous film including a metal oxide containing lithium, the structure of the positive electrode is simplified, and its preparation is simplified. The positive electrode is permeable to gases such as oxygen or air. Therefore, the positive electrode is different from the positive electrode of the prior art, which is substantially impermeable to gases such as oxygen or air and only conducts ions. When the positive electrode is porous and / or gas permeable, oxygen and / or air easily diffuse into the positive electrode, and lithium ions and / or electrons easily move through the lithium-containing metal oxide included in the positive electrode, and thus, electrochemical reactions with oxygen, lithium ions and electrons are easily performed in the positive electrode.
[0226] In addition to the porous film including the lithium-containing metal oxide, the positive electrode may include, for example, other suitable positive electrode materials.
[0227] The positive electrode further includes, for example, a conductive material. This conductive material is, for example, porous. When the conductive material is porous, air penetration is facilitated. The conductive material can use any suitable material having porosity and / or conductivity, and the conductive material is, for example, a metallic material. The metallic material is, for example, a metal fiber, a metal mesh or a metal powder. The metal powder is, for example, copper, silver, nickel or aluminum. The conductive material is, for example, an organic conductive material. The organic conductive material is, for example, a polyphenylene derivative and a polythiophene derivative. The conductive material is, for example, used alone or as a mixture. The positive electrode includes a composite conductor as the conductive material, and in addition to the composite conductor, the positive electrode may further include the aforementioned conductive material.
[0228] The positive electrode is prepared, for example, by mixing a conductive material, an oxygen oxidation / reduction catalyst and a binder, adding a suitable solvent to prepare a positive electrode slurry, and applying the slurry on the substrate surface and drying the slurry, or pressing and molding on the substrate to increase the electrode density. The substrate is, for example, a positive electrode collector, a separator or a solid electrolyte membrane. The positive electrode collector is, for example, a gas diffusion layer. The conductive material includes a composite conductor, and the oxygen oxidation / reduction catalyst and the binder can be omitted from the positive electrode. A more specific method for preparing the positive electrode can refer to the method for preparing the positive electrode described below.
[0229] The lithium-air battery includes a negative electrode. The negative electrode includes lithium.
[0230] The negative electrode is, for example, a lithium metal film or a lithium-based alloy film. The lithium-based alloy is, for example, an alloy of aluminum, tin, magnesium, indium, calcium, titanium or vanadium and lithium.
[0231] Lithium-air batteries include an electrolyte layer disposed between a positive electrode and a negative electrode.
[0232] The thickness of the electrolyte layer may be, for example, about 1 μm to about 1000 μm, about 1 μm to about 500 μm, about 1 μm to about 300 μm, about 1 to about 200 μm, about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 30 μm, about 1 μm to about 20 μm, or about 1 μm to about 10 μm.
[0233] The electrolyte layer includes at least one of a solid electrolyte, a gel electrolyte, or a liquid electrolyte. The solid electrolyte, the gel electrolyte, and the liquid electrolyte are not limited, and any suitable electrolyte may be used.
[0234] The solid electrolyte includes at least one of the following: a solid electrolyte including an ion-conductive inorganic material, a solid electrolyte including a polymer ionic liquid (PIL) and a lithium salt, a solid electrolyte including an ion-conductive polymer and a lithium salt, or a solid electrolyte including an electron-conductive polymer. However, it is not limited thereto, and any suitable solid electrolyte can be used.
[0235] The ion-conductive inorganic material includes at least one of the following: a glass or amorphous metal ion conductor, a ceramic-activated metal ion conductor, or a glass-ceramic-activated metal ion conductor. However, it is not limited thereto, and any suitable ion-conductive inorganic material can be used. The ion-conductive inorganic material is, for example, an ion-conductive inorganic particle or a formed product thereof in the form of a sheet.
[0236] The ion-conductive inorganic material is, for example, at least one of the following: BaTiO 3 、Pb(Zr a Ti 1-a )O 3 (PZT)(0 ≤ a ≤ 1), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT)(0 ≤ x < 1, 0 ≤ y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT), HfO 2 、SrTiO 3 、SnO 2 、CeO 2 、Na 2 O、MgO、NiO、CaO、BaO、ZnO、ZrO 2 、Y 2 O 3 、Al 2 O 3 、TiO 2 、SiO 2 、SiC、 lithium phosphate (Li 3 PO 4 )、 lithium titanium phosphate (Li x Ti y (PO 4 ) 3 ,0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO 4 ) 3 ,0 < x < 2, 0 < y < 1, 0 < z < 3), Li 1+x+y (Ala Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1), lithium lanthanum titanate (Li x La y TiO 3 , 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS 2 -like glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P 2 S 5 -like glass Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), Li 2 O, LiF, LiOH, Li 2 CO 3 、LiAlO 2 、ceramics based on Li 2 O - Al 2 O 3 -SiO 2 -P 2 O 5 -TiO 2 -GeO 2 、or garnet-based ceramics (Li 3+x La 3 M 2 O 12 ( 0≤x≤4 , M = Te, Nb, or Zr)).
[0237] PIL includes, for example, repeating units containing: i) ammonium-based cations, pyrrolidine -based cations, pyridine -based cations, pyrimidine -based cations, imidazole -based cations, piperidine Cations based on pyrazole Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, or triazole at least one of the cations of 4 - PF 6 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - ,(CF 3 SO 2 ) 2 N - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - 、NO 3 - 、Al 2 Cl 7 - , CH 3 COO - ,(CF 3 SO 2 ) 3 C - ,(CF 3 ) 2 PF 4- ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , SF 5 CF 2 SO 3 - , SF 5 CHF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , or (O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - The PIL is, for example, polybis(trifluoromethanesulfonyl)imide (TFSI) (diallyldimethylammonium), poly(bis(trifluoromethanesulfonyl)imide 1-allyl-3-methylimidazole ), or poly(bis(trifluoromethanesulfonyl)imide-N-methyl-N-propylpiperidinium ).
[0238] The ion-conducting polymer includes, for example, at least one ion-conducting repeating unit selected from an ether-based monomer, an acrylic monomer, a methacrylic monomer, or a siloxane-based monomer.
[0239] Ion-conducting polymers include, for example, polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyvinyl sulfone, polypropylene oxide (PPO), polymethyl methacrylate, polyethyl methacrylate, polydimethylsiloxane, polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polyethyl acrylate, poly2-ethylhexyl acrylate, polybutyl methacrylate, poly2-ethylhexyl methacrylate, polydecyl acrylate, polyethylene vinyl acetate, phosphate polymers, polyester sulfide, polyvinylidene fluoride (PVF), or Li-substituted Nafion, but are not limited thereto, and any suitable ion-conducting polymer may be used.
[0240] The electron conductive polymer is, for example, a polyphenylene derivative or a polythiophene derivative, but is not limited thereto, and any suitable electron conductive polymer may be used.
[0241] The gel electrolyte is obtained, for example, by additionally adding a solvent having a low molecular weight to a solid electrolyte located between the positive electrode and the negative electrode. The gel electrolyte is, for example, a gel electrolyte obtained by additionally adding a solvent and an oligomer as a compound having a low molecular weight to a polymer.
[0242] The liquid electrolyte includes a solvent and a lithium salt.
[0243] The solvent may include at least one of an organic solvent, an ionic liquid, or an oligomer, but is not limited thereto, and any suitable material may be used as long as it is liquid at room temperature (25° C.) and functions as a solvent.
[0244] The organic solvent includes, for example, at least one of an ether-based solvent, a carbonate-based solvent, an ester-based solvent, or a ketone-based solvent. The organic solvent includes, for example, at least one of propylene carbonate, ethylene carbonate, fluoroethylene carbonate, vinylethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, dimethylacetamide, dimethyl Sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, succinonitrile, diethylene glycol dimethyl ether (DEGDME), tetraethylene glycol dimethyl ether (TEGDME), polyethylene glycol dimethyl ether (PEGDME, Mn=~500), dimethyl ether, diethyl ether, dibutyl ether, or dimethoxyethane, but are not limited thereto, and any suitable organic solvent that is a solvent at room temperature can be used.
[0245] The ionic liquid (IL) includes, for example, i) at least one of the following: an ammonium-based cation, a pyrrolidine-based cation Cations based on pyridine Cationic, pyrimidine-based Cation, imidazole-based Cation, based on piperidine Cations based on pyrazole Cations, based on Azoles Cationic, pyridazine-based Cations, based on cations based on sulfonium, cations based on triazole cation, and ii) at least one anion of: BF 4 - PF 6 - , AsF 6 - , SbF 6 - 、AlCl 4 - , HSO 4 - , ClO 4 - , CH 3 SO 3 - CF 3 CO 2 - ,(CF 3 SO 2 ) 2 N - , Cl - Br - ,I - 、SO 4 2- CF 3 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - 、NO 3 - 、Al 2 Cl 7 -, CH 3 COO - ,(CF 3 SO 2 ) 3 C - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , SF 5 CF 2 SO 3 - , SF 5 CHF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , or (O(CF 3 ) 2 C 2 (CF 3 ) 2 O) 2 PO - .
[0246] The lithium salt includes at least one of the following: LiTFSI(LiN(SO 2 CF 3 ) 2 )、LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiNO 3 、Lithium bis(oxalate)borate (LiBOB), LiN(SO 2 C2 F 5 ) 2 、LiC(SO 2 CF 3 ) 3 、LiN(SO 3 CF 3 ) 2 ,LiC 4 F 9 SO 3 、LiAlCl 4 , or lithium trifluoromethanesulfonate (LiTfO, LiCF 3 SO 3 ), but is not limited thereto, and any suitable lithium salt may be used. The concentration of the lithium salt is, for example, about 0.01M to about 5.0M.
[0247] The lithium-air battery further includes a separator, for example, between the positive electrode and the negative electrode. The separator is not limited as long as it has a composition that tolerates the use range of the lithium-air battery. The separator includes, for example, a polymer nonwoven such as a nonwoven of a polypropylene material, a nonwoven of a polyphenylene sulfide material, an olefin-based resin such as a porous film of polyethylene or polypropylene, or glass fiber, and may include two or more thereof in combination.
[0248] The electrolyte layer has, for example, a structure in which a separator is impregnated with a solid polymer electrolyte or a structure in which a separator is impregnated with a liquid electrolyte. The electrolyte layer in which a separator is impregnated with a solid polymer electrolyte is prepared, for example, by disposing a solid polymer electrolyte membrane on one side or both sides of a separator and then rolling them simultaneously. The electrolyte layer in which a separator is impregnated with a liquid electrolyte is prepared by injecting a liquid electrolyte including a lithium salt into the separator.
[0249] The lithium-air battery is completed by disposing a negative electrode at one side in a case, disposing an electrolyte layer on the negative electrode, disposing a positive electrode on the electrolyte layer, placing a porous positive electrode collector on the positive electrode, disposing a pressurizing member on the porous positive electrode collector to transfer air to the air electrode, and pressurizing the pressurizing member to fix the unit cell. The case may be divided into an upper portion contacting the positive electrode and a lower portion contacting the negative electrode, and an insulating resin may be disposed between the upper portion and the lower portion to electrically insulate the positive electrode and the negative electrode.
[0250] Lithium-air batteries can be used in all kinds of primary and secondary batteries. The shape of lithium-air batteries is not particularly limited, but is, for example, coin-type, button-type, sheet-type, stacked type, cylindrical type, flat type, or angular type. Lithium-air batteries can be large batteries used in electric vehicles.
[0251] An embodiment of a lithium-air battery is schematically shown in Figure 8In. The lithium-air battery 500 includes a first electrolyte layer 400, which is disposed between a positive electrode 200 using oxygen as an active material adjacent to a first current collector 210 and a negative electrode 300 containing lithium adjacent to a second current collector 310. The first electrolyte layer 400 is a separator impregnated with a liquid electrolyte. The second electrolyte layer 450 is disposed between the positive electrode 200 and the first electrolyte layer 400. The second electrolyte layer 450 is a lithium ion conductive solid electrolyte membrane. The first current collector 210 is porous and may function as a gas diffusion layer capable of diffusing air. Alternatively, a gas diffusion layer may be additionally disposed between the first current collector 210 and the positive electrode 200. A pressurizing member 220 is disposed on the first current collector 210 for transferring air to the positive electrode. A shell 320 of an insulating resin material is disposed between the positive electrode 200 and the negative electrode 300 to electrically isolate the positive electrode 200 and the negative electrode 300. Air is supplied through an air inlet 230a and discharged through an air outlet 230b. The lithium-air battery 500 may be housed in a stainless steel container.
[0252] The "air" of the lithium-air battery is not limited to air, but may include a combination of gases including oxygen, or pure oxygen. This broad definition of the term "air" applies to all applications such as air batteries and air electrodes.
[0253] The method for preparing a positive electrode according to an embodiment includes: preparing a composition including a metal oxide and a binder; applying the composition to a substrate and drying the composition to prepare a coating; pressing the coating to prepare a sheet; and heat-treating the sheet in an oxidative atmosphere at a temperature of about 450° C. to about 800° C. The metal oxide may include, for example, a lithium-containing metal oxide.
[0254] The composition may include, for example, the lithium-containing metal oxide, a binder, a dispersant, a plasticizer, and a solvent. The type and amount of the binder, dispersant, or plasticizer are not particularly limited, and all of the raw sheets used to form ceramics in the art can be used. Based on 100 parts by weight of the lithium-containing metal oxide, for example, about 5 parts by weight to about 20 parts by weight of a binder, about 1 part by weight to about 10 parts by weight of a dispersant, and about 1 part by weight to about 10 parts by weight of a plasticizer may be included. The composition may further include a solvent. The amount of the solvent may be, for example, about 1 part by weight to about 500 parts by weight, based on 100 parts by weight of the solid content of the lithium-containing metal oxide, the binder, the dispersant, and the plasticizer.
[0255] As the binder, for example, polyvinyl butyral, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butylene rubber or fluororubber may be used.
[0256] As the solvent, alcohol such as ethanol or NMP may be used. The amount of the solvent is appropriately controlled to dissolve or disperse the components constituting the composition.
[0257] The composition may further include organic particles having a size of about 1 μm or more.
[0258] The size (average particle size) of the organic particles is an important factor affecting the size of the large diameter pores in the positive electrode, and is, for example, about 1 μm to about 100 μm, for example, about 2 μm to about 50 μm. , for example, about 3 μm to about 30 μm, for example, about 4 μm to about 20 μm, for example, about 5 μm to about 10 μm, for example, about 6 μm to about 8 μm. The organic particles are microspheres with a unimodal particle size distribution. When analyzed using dynamic light scattering (DLS, Nicomp 380), the unimodal particle size distribution can be defined within a standard deviation of less than about 40%, for example, about 10% or less, for example, about 1% to about less than about 40%, for example, about 3% to about 10%. The organic particles may have a spherical, rod-shaped, elliptical or radial shape. In the case of a spherical shape, the organic particles may be, for example, microspheres having an average particle size of about 1 μm or more. In the case where the size of the particles is less than about 1 μm, the discharge product content decreases, and the charge and discharge efficiency and life characteristics of a lithium-air battery employing such a positive electrode may be deteriorated.
[0259] The organic particles may be polymers, and may include, for example, at least one of: i) polystyrene, copolymers containing styrene repeating units, copolymers containing repeating units having crosslinkable functional groups, or ii) crosslinked polymers. The particles may be polymers containing styrene-based repeating units. As described, polymers having styrene-based repeating units have hydrophobicity, do not adversely affect the lithium metal electrode, have low electrolyte wettability, and thus can minimize the reactivity of the lithium metal electrode and the electrolyte.
[0260] At least one of i) polystyrene, a copolymer comprising a styrene repeating unit, a copolymer comprising a repeating unit having a crosslinkable functional group, or ii) a crosslinked polymer may be at least one of polystyrene, a poly(styrene-divinylbenzene) copolymer, a poly(methyl methacrylate-divinylbenzene) copolymer, a poly(ethyl methacrylate-divinylbenzene) copolymer, a poly(pentyl methacrylate-divinylbenzene) copolymer, a poly(butyl methacrylate-divinylbenzene) copolymer, a poly(propyl methacrylate-divinylbenzene) copolymer, a poly(styrene-ethylene-butylene-styrene) copolymer, a poly(styrene-methyl methacrylate) copolymer, a poly(styrene-acrylonitrile) copolymer, a poly(styrene-vinylpyridine) copolymer, a poly(acrylonitrile-butadiene-styrene) copolymer, a poly(acrylonitrile-ethylene-propylene-styrene) copolymer, a poly(methyl methacrylate-acrylonitrile-butadiene-styrene) copolymer, a poly(methacrylate-butadiene-styrene) copolymer, a poly(styrene-acrylonitrile) copolymer, and a poly(acrylonitrile-styrene-acrylate) copolymer, or a crosslinked polymer.
[0261] The poly(styrene-divinylbenzene) copolymer is represented by Formula 17:
[0262] Formula 17
[0263]
[0264] In Formula 17, a and b are mole fractions and are respectively about 0.01 to about 0.99, and the sum of a and b is 1. In Formula 17, a is, for example, about 0.95 to about 0.99, or about 0.98 to about 0.99, and b is, for example, about 0.01 to about 0.05, or about 0.01 to about 0.02.
[0265] The poly(styrene-divinylbenzene) copolymer is represented by Formula 18:
[0266] Formula 18
[0267]
[0268] The poly(acrylonitrile-butadiene-styrene) copolymer is represented by Formula 19:
[0269] Formula 19
[0270]
[0271] In Formula 19, x, y, and z are each independently a mole fraction of about 0.01 to about 0.99, and the sum of x, "y," and z is 1.
[0272] In Formula 19, x is about 0.1 to about 0.35, y is about 0.05 to about 0.55, and z is about 0.2 to about 0.7. For example, x is about 0.15 to about 0.35, y is about 0.05 to about 0.3, and z is about 0.4 to about 0.6.
[0273] The degree of polymerization of the poly(styrene-divinylbenzene) copolymer and the poly(acrylonitrile-butadiene-styrene) copolymer is a number of about 2 to about 5,000, such as about 5 to about 1,000.
[0274] The poly(styrene-divinylbenzene) copolymer and the poly(acrylonitrile-butadiene-styrene) copolymer may be, for example, a block copolymer.
[0275] The amount of organic particles in the composition is from about 1 part by weight to about 60 parts by weight, from about 5 parts by weight to about 60 parts by weight, or from about 20 parts by weight to about 60 parts by weight, based on 100 parts by weight of the metal oxide (mixed conductor). The amount of the binder is from about 5 parts by weight to about 50 parts by weight, for example, from about 10 parts by weight to about 40 parts by weight, based on 100 parts by weight of the metal oxide (mixed conductor). If the amounts of the organic particles and the binder are within these ranges, a positive electrode having excellent capacity, electronic conductivity and ionic conductivity, and excellent physical properties can be prepared.
[0276] The coating layer may be prepared by applying the composition to a thickness of about 1 μm to about 1000 μm on a substrate such as a release film using a doctor blade, and then drying the composition.
[0277] The operation of preparing a sheet by pressing a coating may include: stacking a plurality of coatings to prepare a stack; and pressing the stack to prepare a sheet. For example, a plurality of coatings disposed on a release film are prepared, and the coatings are stacked to face each other and pressed to prepare a raw sheet. The pressing may be performed by a heat press using a constant pressure for about 1 minute to about 30 minutes at a pressure of about 100 psi to about 500 psi.
[0278] The heat treatment of the sheet thus prepared is carried out in a temperature range capable of decomposing organic particles to form pores, for example, at about 450°C to about 800°C, for example, at about 450°C to about 750°C, for example, at about 450°C to about 700°C. If the composition includes a binder, the binder may also be removed during the heating process. The heating time varies depending on the heating temperature, but is, for example, from about 0.5 hours to about 20 hours, from about 1 hour to about 10 hours, or from about 1 hour to about 3 hours. By heat treatment, organic materials such as binders in the raw sheet are stably decomposed and removed, and a stable and firm porous film is prepared. The temperature increase rate to the heat treatment temperature during the heat treatment may be, for example, 5 degrees / minute, and the cooling may be natural cooling. By heat treatment within such a temperature and time range, a positive electrode having excellent capacity properties can be prepared, and by using the positive electrode, a lithium-air battery having improved charge and discharge efficiency and life characteristics can be formed.
[0279] Reference Figures 7A to 7C , a method for preparing a positive electrode will be described.
[0280] A composition including a lithium-containing metal oxide 11 and organic particles 12 is applied to a substrate 10 such as a release film using a doctor blade and then dried to prepare a coating. Then, a plurality of coatings are arranged to face each other and pressed to prepare a sheet 20. The sheet 20 is heat-treated to remove the organic particles 12 and form a porous film 50 including large-diameter pores 13 and small-diameter pores 14. The porous film 50 is used as a positive electrode 100.
[0281] Hereinafter, the present disclosure will be described in more detail with reference to Examples and Comparative Examples. However, these Examples are for illustrating the present disclosure, and the scope of the present disclosure is not limited thereto.
[0282] Example
[0283] Preparation of lithium-containing metal oxides
[0284] Preparation Example 1: Li 4.5 Ti 4.5 Nb 0.5 O 12-δ Preparation of spinel materials
[0285] Mix the lithium precursor Li in a stoichiometric ratio 2 CO 3 , titanium precursor TiO 2 and Nb precursor Nb 2 O 5, then grind and mix at 280 rpm using a ball mill including ethanol and zirconia balls for 4 hours to prepare a mixture. The mixture thus obtained is dried at 90°C for 6 hours, and a first heat treatment is performed at 700°C in an air atmosphere for 5 hours. The resulting product of the first heat treatment is ground using a ball mill, and then pressed under isostatic pressing to prepare a sheet (circular wafer). The sheet thus prepared is subjected to a second heat treatment at 950°C in a reducing atmosphere for 24 hours to prepare a composite conductor. The reducing atmosphere is an atmosphere having 5% hydrogen and 95% argon. The composition of the lithium-containing metal oxide thus prepared is Li 4.5 Ti 4.5 Nb 0.5 O 12-δ (0<δ<3).
[0286] Preparation Example 2: Li 3.5 Ti 4.0 Nb 1.0 O 12-δ Preparation of spinel materials
[0287] A composite conductor was prepared by the same method as in Preparation Example 1, except that the stoichiometric ratio of the lithium precursor, the titanium precursor, and the Nb precursor was changed.
[0288] The composition of the lithium-containing metal oxide prepared in this way is Li 3.5 Ti 4.0 Nb 1.0 O 12-δ (0<δ<3).
[0289] Preparation Example 3: Li 3.5 Ti 4.0 Ta 1.0 O 12-δ Preparation of spinel materials
[0290] The composite conductor was prepared by the same method as in Preparation Example 1, except that the Ta precursor Ta was used. 2 O 5 The Nb precursor was replaced, and the stoichiometric ratios of the lithium precursor, the titanium precursor, and the Ta precursor were changed.
[0291] The composition of the lithium-containing metal oxide prepared in this way is Li 3.5 Ti 4.0 Ta 1.0 O 12-δ (0<δ<3).
[0292] Preparation Example 4: Li 4.5 Ti 4.5 G 0.5 O 12-δ Preparation of spinel materials
[0293] A composite conductor was prepared by the same method as in Preparation Example 1, except that a Gd precursor Gd was used. 2 O 3 Replace Nb precursor.
[0294] The composition of the lithium-containing metal oxide prepared in this way is Li 4.5 Ti 4.5 G 0.5 O 12-δ (0<δ<3).
[0295] Preparation Example 5: Li 5.0 Ti 4.0 G 1.0 O 12-δ Preparation of spinel materials
[0296] A composite conductor was prepared by the same method as in Preparation Example 1, except that a Gd precursor Gd was used. 2 O 3 The Nb precursor was replaced, and the stoichiometric ratios of the lithium precursor, the titanium precursor, and the Gd precursor were changed.
[0297] The composition of the lithium-containing metal oxide prepared in this way is Li 5.0 Ti 4.0 G 1.0 O 12-δ (0<δ<3).
[0298] Preparation Example 6: Li 4.5 Ti 4.5 In 0.5 O 12-δ Preparation of spinel materials
[0299] The composite conductor was prepared by the same method as in Preparation Example 1, except that the In precursor In was used. 2 O 3 Replace Nb precursor.
[0300] The composition of the lithium-containing metal oxide prepared in this way is Li 4.5 Ti 4.5 In 0.5 O 12-δ (0<δ<3).
[0301] Preparation Example 7: Li 5.0 Ti 4.0 In 1.0 O 12-δ Preparation of spinel materials
[0302] The composite conductor was prepared by the same method as in Preparation Example 1, except that the In precursor In was used.2 O 3 The Nb precursor was replaced, and the stoichiometric ratios of the lithium precursor, the titanium precursor, and the In precursor were changed.
[0303] The composition of the lithium-containing metal oxide prepared in this way is Li 5.0 Ti 4.0 In 1.0 O 12-δ (0<δ<3).
[0304] Preparation Example 8: Li 4 Ti 5 O 12 Preparation of spinel materials
[0305] Commercially purchased Li 4 Ti 5 O 12 To be used as supplied.
[0306] Preparation Example 9: Li 0.34 La 0.55 TiO 3 Preparation of perovskite materials
[0307] According to Li 0.34 La 0.55 TiO 3 The composition ratio of Li 2 CO 3 ,La 2 O 3 and TiO 2 The powder was added to ethanol and mixed. The amount of ethanol was about 4 parts by weight based on 100 parts by weight of Li 2 CO 3 ,La 2 O 3 and TiO 2 Total weight of powder.
[0308] The mixture was put into a ball mill and ground and mixed for 4 hours. The obtained mixture was dried and heated to 800° C. at a temperature increase rate of about 5° C. / min, and then subjected to a first heat treatment at the same temperature in an air atmosphere for 4 hours.
[0309] The powder obtained by the first heat treatment is ground to prepare a powder having a primary particle size of about 0.3 μm. The powder thus prepared is pressed to form a cylindrical tablet having a diameter of about 1.3 cm, a height of about 0.5 cm and a weight of about 0.3 g. The tablet thus formed is subjected to a second heat treatment at a temperature of 1100° C. for about 24 hours in an air atmosphere to obtain the target material. The temperature increase rate for the second heat treatment to increase the temperature to 1100° C. is about 5° C. / minute. The composition of the lithium-containing metal oxide thus prepared is Li 0.34 La 0.55 TiO 3 .
[0310] Preparation Example 10: Li 0.34 La 0.55 RuO 3 Preparation of perovskite materials
[0311] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that RuO 2 Replace TiO 2 And a second heat treatment is performed at 1,200°C.
[0312] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 RuO 3 .
[0313] Preparation Example 11: Li 0.34 La 0.55 MnO 3 Preparation of perovskite materials
[0314] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that MnO 2 Replace TiO 2 And a second heat treatment is performed at 1,200°C.
[0315] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 MnO 3 .
[0316] Preparation Example 12: Li 0.34 La 0.55 NiO 3 Preparation of perovskite materials
[0317] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that Ni(OH) 2 Replace TiO 2And a second heat treatment is performed at 1,200°C.
[0318] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 NiO 3 .
[0319] Preparation Example 13: Li 0.34 La 0.55 CrO 3 Preparation of perovskite materials
[0320] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that Cr 2 O 3 Replace TiO 2 And a second heat treatment is performed at 1,200°C.
[0321] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 CrO 3 .
[0322] Preparation Example 14: Li 0.34 La 0.55 Ir 3 Preparation of perovskite materials
[0323] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that IrO 2 Replace TiO 2 And a second heat treatment is performed at 1,200°C.
[0324] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 Ir 3 .
[0325] Preparation Example 15: Li 0.34 La 0.55 CoO 3 Preparation of perovskite materials
[0326] The target material was obtained by carrying out the same procedure as in Preparation Example 9, except that Co 2 O 3 Replace TiO 2 And a second heat treatment is performed at 1,200°C.
[0327] The composition of the lithium-containing metal oxide prepared in this way is Li 0.34 La 0.55 CoO 3 .
[0328] Preparation of positive electrode
[0329] Example 1
[0330] Li prepared according to Preparation Example 10 0.34 La 0.55 RuO 3 (hereinafter LLRuO) was ground in a ball mill, and a powder having a primary particle size of about 300 nm was obtained.
[0331] 500 mg of the thus obtained LLRuO powder, 150 mg of polyvinyl butyral resin (Butvar B79: Eastman Co.) as a binder, 150 mg of poly(styrene-b-divinylbenzene) copolymer microspheres (hereinafter referred to as "PS MS") (average particle size: about 3 μm) (EPRUI Co.) and ethanol (Samchun Chemical Co.) as a solvent were mixed to prepare slurry. In the block copolymer, the mixing weight ratio of the polystyrene block and the polydivinylbenzene block was about 80:20 (4:1).
[0332] The slurry thus obtained was coated on a PET release film to a thickness of 200 μm using a doctor blade, and dried in air to prepare a partially dried coating.
[0333] The coating thus prepared was cut into 7×7 cm pieces on a PET release film. 2 The two coating layers cut into the size were stacked to face each other and laminated by a hot press at 250 psi at 100° C. for 15 minutes.
[0334] Then, the PET release film was removed to obtain a green sheet. The green sheet thus obtained was dried at 25° C. and heat-treated at 450° C. for 1 hour in an air atmosphere to prepare a positive electrode including a lithium-containing metal oxide and large-diameter pores in the form of a porous film.
[0335] The weight per unit area (loading level) of the positive electrode as a porous film is about 4.5 mg / cm 2 to about 6.5 mg / cm 2 , and a thickness thereof is about 25 μm to about 45 μm.
[0336] The amount of the PS MS was 30 parts by weight based on 100 parts by weight of LLRuO, and the amount of the polyvinyl butyral resin binder was 30 parts by weight based on 100 parts by weight of LLRuO.
[0337] The relative volume ratios of LLRuO, binder, and PS MS used to prepare the porous membrane were 21.3:41.2:37.5.
[0338] Scanning electron microscope images of a cross section of a dried green sheet before heat treatment and a cross section of a positive electrode having a porous film prepared therefrom are shown in FIG. Figure 3A and 3B middle.
[0339] Figure 3A is a scanning electron microscope image of a cross section of a dried green sheet before heat treatment. Figure 3A The PS MS particles are shown to be dispersed in the LLRuO matrix.
[0340] Figure 3B is a scanning electron microscope image of a cross section of a positive electrode in the form of a porous film after heat treatment. Figure 3B It is shown that the film including LLRuO includes a plurality of large diameter pores.
[0341] Despite Figure 3B It is not clearly shown in the figure, but the presence of multiple small-diameter holes (not shown) is confirmed in the magnified image.
[0342] The large diameter pores are formed by thermal decomposition of the PS MS particles, and the small diameter pores are formed by thermal decomposition of the binder.
[0343] It was confirmed that the porous film included large-diameter pores having a size of about 3 μm and small-diameter pores having a size of about 1 μm or less.
[0344] The porosity of the porous film is obtained by measuring the area of the porous film using an optical microscope, measuring the thickness of the porous film using a SEM, and calculating the volume of the porous film.
[0345] The porosity of the porous membrane is calculated using the volume thus calculated and the weight of the porous membrane. The porosity is the volume percentage occupied by all pores including large-diameter pores and small-diameter pores in the total volume of the porous membrane.
[0346] The amount of large-diameter pores included in the porous membrane was confirmed from the relative volumes of LLRuO, the binder, and the PS MS used to prepare the porous membrane of Example 1.
[0347] The amount of large diameter pores is the volume percentage occupied by large diameter pores relative to the total volume of large diameter pores, small diameter pores and LLRuO. That is, the percentage of large diameter pores is the volume percentage occupied by large diameter pores in the total volume of the porous film.
[0348] The size of the large diameter pores was about 3 μm. The amount of the large diameter pores was about 37.5% by volume. The porosity of the porous membrane was about 71.5%.
[0349] Example 2
[0350] A positive electrode having a porous shape was prepared by performing the same method as in Example 1, except that the amount of PSMS was changed to 300 mg.
[0351] The amount of the PS MS was 60 parts by weight based on 100 parts by weight of LLRuO, and the amount of the polyvinyl butyral resin binder was 30 parts by weight based on 100 parts by weight of LLRuO.
[0352] The size of the large diameter pores was about 3 μm. The amount of the large diameter pores was about 54.5% by volume. The porosity of the porous membrane was about 84%.
[0353] Example 3
[0354] A positive electrode was prepared by performing the same method as in Example 1, except that the average particle size of the PS MS was changed to about 8 μm.
[0355] The amount of the PS MS was 30 parts by weight based on 100 parts by weight of LLRuO, and the amount of the polyvinyl butyral resin binder was 30 parts by weight based on 100 parts by weight of LLRuO.
[0356] The size of the large diameter pores was about 8 μm. The amount of the large diameter pores was about 37.5% by volume. The porosity of the porous membrane was about 71.5%.
[0357] Example 4
[0358] A positive electrode was prepared by performing the same method as in Example 1, except that the amount of the binder was changed to 100 mg.
[0359] The amount of the PS MS was 30 parts by weight based on 100 parts by weight of LLRuO, and the amount of the polyvinyl butyral resin binder was 20 parts by weight based on 100 parts by weight of LLRuO.
[0360] The size of the large diameter pores was about 3 μm. The amount of the large diameter pores was about 43% by volume. The porosity of the porous membrane was about 75%.
[0361] Reference Example 1
[0362] By the same method as in Example 1, a slurry was prepared.
[0363] The slurry thus prepared was placed on a PET release film using a doctor blade and dried in air for 12 hours to prepare a coating layer.
[0364] The coating layer thus prepared was heated at 450° C. for 1 hour to prepare a positive electrode in the form of a porous film.
[0365] Lithium-air battery manufacturing
[0366] Example 5: Fabrication of a lithium-air battery (positive electrode / LATP / electrolyte / Li negative electrode)
[0367] A separator (Celgard 3501) was placed on the lithium metal foil negative electrode.
[0368] 0.2 ml of an electrolyte in which 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dissolved in propylene carbonate (PC) was injected into the separator to prepare a negative electrode intermediate layer.
[0369] A LATP solid electrolyte membrane (250 μm in thickness, Ohara Corp., Japan) was disposed on the separator to prepare a lower structure consisting of anode / anode intermediate layer / solid electrolyte layer.
[0370] The lower structure is covered with a bag of aluminum coated on polyolefin. A window having a certain size is provided on the bag to expose the LATP solid electrolyte outside the bag.
[0371] The positive electrode prepared in Example 1 was placed on the LATP solid electrolyte exposed outside the bag. Then, a gas diffusion layer (GDL, SGL Co., 25BC) was placed on top of the positive electrode, a nickel mesh was placed on the gas diffusion layer, and a pressurizing member for supplying air to the positive electrode was pressurized to fix the unit cell, thereby preparing a lithium-air battery.
[0372] Examples 6 to 8
[0373] A lithium-air battery was prepared by the same method as in Example 5, except that the positive electrode prepared in Example 2-4 was used instead of the positive electrode prepared in Example 1.
[0374] Reference Example 2
[0375] A lithium-air battery was prepared by the same method as in Example 5, except that the positive electrode prepared in Reference Example 1 was used instead of the positive electrode prepared in Example 1.
[0376] Evaluation Example 1: Evaluation of surface roughness
[0377] The roughness of the surface of the positive electrodes including the porous films prepared in Example 1 and Reference Example 1 was evaluated using AFM.
[0378] The evaluation results are shown in Figure 1 and 2 And Table 1.
[0379] Figure 1 is an AFM image of the surface of a porous membrane flattened by a hot press as prepared in Example 1.
[0380] Figure 2is an AFM image of the surface of the non-pressurized porous membrane prepared in Reference Example 1.
[0381] In Table 1, R q is the RMS roughness of the porous membrane surface (R q ).
[0382] In Table 1, R a is the average roughness of the surface of the porous membrane (R a ).
[0383] In Table 1, R max is the maximum roughness depth of the porous membrane surface (R max ).
[0384] Measuring R from AFM images q , R a and R max .
[0385] Table 1
[0386] <![CDATA[R q [μm]]]> <![CDATA[R a [μm]]]> <![CDATA[R max [μm]]]> Reference Example 1 1.482 1.126 12.634 Example 1 0.275 0.212 2.303
[0387] As shown in Table 1, the surface of the porous film prepared in Reference Example 1 has an R q Value, R greater than 10μm max value and R greater than 1.0μm a value.
[0388] Compared with Reference Example 1, the surface of the porous film prepared in Example 1 had reduced surface roughness.
[0389] Evaluation Example 2: Evaluation of charging and discharging characteristics of lithium-air batteries
[0390] When using calcium hydroxide (Ca(OH) 2 )Removal of CO 2 Then, charging and discharging were performed in an oxygen atmosphere at 40° C., 1 atmosphere (atm), and 100% relative humidity.
[0391] The lithium-air batteries prepared in Example 5 and Reference Example 2 were subjected to a charge and discharge cycle comprising the following steps: 2 The cells were discharged at a constant current to 2.0 V (vs. Li), charged at the same current to 4.5 V, and then charged at a constant voltage at 4.5 V until the current dropped to 0.006 mA / cm 2 (Chemical transformation step).
[0392] Then, the lithium-air battery was charged at 0.6 mA / cm 2The cells were discharged at a constant current to 2.0 V (vs. Li), charged at the same current to 4.5 V, and then charged at a constant voltage at 4.5 V until the current dropped to 0.06 mA / cm 2 , and perform this charge and discharge cycle.
[0393] By providing 3 mAh / cm 2 The life characteristics were evaluated by the number of cycles corresponding to the cut-off discharge capacity of 80%.
[0394] like Figure 4 As shown in , the lithium-air battery formed in Example 5 has a lifespan of 34 cycles. Figure 5 As shown in , the lithium-air battery formed in Reference Example 2 has a lifespan of 10 cycles.
[0395] Therefore, the lithium-air battery of Example 5 having low surface roughness exhibited significantly improved cycle characteristics compared to the lithium-air battery of Reference Example 2 having high surface roughness.
[0396] like Figure 6 As shown in , it was confirmed that, at the first cycle of the lithium-air battery formed in Example 5, after discharge, discharge products were uniformly formed in the porous film of the positive electrode and at the surface of the porous film.
[0397] Without wishing to be bound by theory, it is understood that the improved life characteristics of the lithium-air battery of Example 5 can be obtained because the surface roughness of the positive electrode is reduced and thus more uniform contact of the current collector with the positive electrode is possible, and thus the internal resistance is reduced.
[0398] Furthermore, when non-uniform generation of discharge products between the positive electrode and the current collector and in the positive electrode is suppressed in the lithium-air battery of Example 5, generation of discharge products electrically insulated from the current collector is prevented, and reversibility of the electrode reaction improves.
[0399] According to one aspect, by including a porous film containing a metal oxide, chemical stability of a positive electrode and a lithium-air battery is improved, and by using a positive electrode including a porous film that suppresses irregular generation of discharge products, cycle characteristics of a lithium-air battery are improved.
[0400] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for limiting purposes. The description of features, aspects, or advantages in each embodiment should be considered to be applicable to other similar features, aspects, or advantages in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, it will be understood by those of ordinary skill in the art that various changes in form and detail may be made therein without departing from the spirit and scope as defined by the appended claims.
Claims
1. A positive electrode configured to use oxygen as a positive electrode active material, the positive electrode comprising: A porous membrane, wherein the porous membrane comprises a lithium-containing metal oxide, and wherein the surface of the porous membrane has a root mean square roughness of 0.01 μm to 1 μm, and the porosity of the porous membrane is 50 vol% to 99 vol%, based on the total volume of the porous membrane.
2. The positive electrode according to claim 1, wherein the average roughness of the surface of the porous membrane is 0.01 μm to 1 μm.
3. The positive electrode according to claim 1, wherein the maximum roughness depth of the surface of the porous membrane is 0.1 μm to 10 μm.
4. The positive electrode according to claim 1, wherein the porous membrane comprises large-diameter pores, and the size of the large-diameter pores is 1 μm or more.
5. The positive electrode according to claim 4, wherein the amount of the large-diameter pores is 30 vol% or higher, based on the total volume of the porous membrane.
6. The positive electrode according to claim 1, wherein the amount of the lithium-containing metal oxide comprised in the porous membrane is 50 wt% or higher, based on the total weight of the porous membrane.
7. The positive electrode according to claim 1, wherein the average particle diameter of the lithium-containing metal oxide is 10 nm to 500 nm.
8. The positive electrode according to claim 1, wherein the lithium-containing metal oxide is a crystalline lithium ion conductor, and wherein the lithium-containing metal oxide has a carbon content of 1.0×10 -7 Ionic conductivity of Siemens / cm or higher.
9. The positive electrode according to claim 1, wherein the lithium-containing metal oxide is a crystalline electronic conductor, and wherein the lithium-containing metal oxide has a -6 Electronic conductivity of Siemens / cm or higher.
10. The positive electrode according to claim 1, wherein the lithium-containing metal oxide is a mixed conductor, and wherein the lithium-containing metal oxide has a 1×10 -6 Siemens / cm or higher electronic conductivity and 1×10 at 25°C -7 Ionic conductivity of Siemens / cm or higher.
11. The positive electrode according to claim 1, wherein the lithium-containing metal oxide comprises at least one of a perovskite compound or a spinel compound.
12. The positive electrode according to claim 1, wherein the lithium-containing metal oxide comprises a perovskite compound represented by Formula 1: Formula 1 Li x A y G z About 3-δ in, In Formula 1, each A and G is independently at least one of Group 2 to Group 16 elements, and 0 < x < 1, 0 < y < 1, 0 < x + y ≤ 1, 0 < z ≤ 1.5, and 0 ≤ δ ≤ 1.
5.
13. The positive electrode according to claim 12, wherein A is at least one of the following: Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, or Er, G is at least one of the following: Ti, Pd, Pb, Fe, Ir, Co, Rh, Mn, Ni, Cr, Ru, Re, Sn, V, Ge, W, Zr, Mo, Hf, U, Nb, Th, Ta, Bi, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Mg, Al, Si, Sc, Zn, Ga, Rb, Ag, Cd, In, Sb, Pt, Au, or Pb, and 0.2 < x ≤ 0.7, 0 < y ≤ 0.7, 0 < x + y < 1, 0 < z ≤ 1.2, and 0 ≤ δ ≤ 1.
2.
14. The positive electrode according to claim 12, wherein A is at least one of the following: La, Ce, Pr, Gd, Ca, Sr, or Ba, G is at least one of the following: Ti, Mn, Ni, Ru, Cr, Co, Ir, Fe, Pd, Pb, Rh, Sn, V, Re, Ge, W, Zr, Mo, Nb, Ta, Hf, or Bi, and 0.2 < x ≤ 0.5, 0.4 < y ≤ 0.7, 0 < x + y < 1, 0.8 < z ≤ 1.2 and 0 ≤ δ ≤ 1.
15. The positive electrode according to claim 12, wherein the perovskite compound has a relative humidity of 1×10 -6 Siemens / cm or higher electronic conductivity and 2×10 at 25°C -7 Ionic conductivity of Siemens / cm or higher.
16. The positive electrode according to claim 1, wherein the lithium-containing metal oxide comprises a spinel compound represented by at least one of Formula 2 or Formula 3: Formula 2 Li 1±x M 2±y O 4-δ1 Formula 3 Li 4±a M 5±b O 12-δ2 in, In Formulas 2 and 3, each M is independently at least one element of Group 2 to Group 16, and 0 < x < 1, 0 < y < 1, 0 ≤ δ1 ≤ 1, 0 < a < 2, 0.3 < b < 5 and 0 ≤ δ2 ≤ 3.
17. The positive electrode according to claim 16, wherein each M is independently at least one of the following: Ni, Pd, Pb, Fe, Ir, Co, Rh, Mn, Cr, Ru, Re, Sn, V, Ge, W, Zr, Ti, Mo, Hf, U, Nb, Th, Ta, Bi, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Pm, Sm, Gd, Tb, Dy, Ho, Er, Mg, Al, Si, Sc, Zn, Ga, Rb, Ag, Cd, In, Sb, Pt, Au, or Pb.
18. The positive electrode according to claim 16, wherein the spinel compound is represented by Formula 4: Formula 4 Li 4±a You 5-b M' c ON 12-δ in, In Formula 4, M' is at least one of the following: Cr, Mg, Ca, Sr, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Zr, Hf, V, Nb, Ta, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Hg, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, Bi, Po, As, Se, or Te, and 0.3 < a < 2, 0.3 < b < 2, 0.3 < c < 2 and 0 ≤ δ ≤ 3.
19. The positive electrode according to claim 16, wherein the spinel compound has a 1×10 -6 Siemens / cm or higher electronic conductivity and 1×10 at 25°C -7 Ionic conductivity of Siemens / cm or higher.
20. The positive electrode according to claim 1, wherein the lithium-containing metal compound comprises at least one of the following: a layered compound, a garnet compound, a NASICON compound, a LISICON compound, a phosphate compound, a lithiophilite compound, a triphylite compound, an antiperovskite compound, a silicate compound, or a borate compound.
21. The positive electrode according to claim 1, wherein the lithium-containing metal compound comprises at least one of the following: a layered compound represented by Formula 5, a NASICON compound represented by Formula 6, a LISICON compound represented by Formula 7, a garnet compound represented by Formula 8, a phosphate compound represented by Formula 9, a phosphate compound represented by Formula 10, a lithiophilite compound represented by Formula 11, a triphylite compound represented by Formula 11, an antiperovskite compound represented by Formula 12, a silicate compound represented by Formula 13, or a borate compound represented by Formula 14: Formula 5 Li 1±x M 1±y O 2±δ in, In Formula 5, M in Formula 5 is at least one element of Group 2 to Group 16, and 0 < x < 0.5, 0 < y < 1 and 0 ≤ δ ≤ 1, Formula 6 Li 1+x A x M 2-x (XO4)3 wherein, in Formula 6, In Formula 6, each of A and M is independently at least one element from Group 2 to Group 16, X is As, P, Mo, or S, and 0 < x < 1, Formula 7 Li 8-c A a B′ b O4 wherein, in Formula 7, each of A and B′ in Formula 7 is independently at least one element from Group 2 to Group 16, c = ma + nb, where m is the oxidation number of A, n is the oxidation number of B′, and 0 < a ≤ 1 and 0 ≤ b ≤ 1, Formula 8 <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> A3B′2O<h2 style=";text-align:left;direction:ltr"> 12 wherein, in Formula 8, each of A and B′ in Formula 8 is independently at least one element from Group 2 to Group 16, and 3 ≤ x ≤ 7, Formula 9 That 1±x MPO4 Formula 10 Li2MP2O7 wherein, in Formulas 9 and 10, each of M in Formulas 9 and 10 is at least one element from Group 2 to Group 16, and 0 ≤ x ≤ 1, Formula 11 Li 1±x M(TO4)X′ wherein, in Formula 11, M in Formula 11 is at least one element from Group 2 to Group 16, T is P or S, X′ is F, O, or OH, and 0 ≤ x ≤ 1.0, Formula 12 Li x M y OH wherein, in Formula 12, M in Formula 12 is at least one element from Group 2 to Group 16, A in Formula 12 is F, Cl, Br, I, S, Se or Te, and 2 ≤ x ≤ 3 and 0 ≤ y ≤ 1, Formula 13 That 2±x MSiO4 wherein, in Formula 13, M is at least one element from Group 2 to Group 16, and 0 ≤ x ≤ 1, Formula 14 That 1±x MBO3 wherein, in Formula 14, M in Formula 14 is at least one element from Group 2 to Group 16, and 0 ≤ x ≤ 1.
22. The positive electrode according to claim 21, wherein the lithium-containing metal oxide has a 1×10 -6 Ionic conductivity of Siemens / cm or higher.
23. The positive electrode according to claim 1, wherein the lithium-containing metal oxide is electrochemically stable at a voltage of 2 V to 4 V relative to lithium metal.
24. The positive electrode according to claim 1, wherein the porous membrane further comprises an electronic conductor represented by at least one of Formula 15 or Formula 16: Formula 15 A x B′ y O 3±δ in, In Formula 15, each of A and B′ in Formula 15 is independently at least one element from Group 2 to Group 16, and 0.8 ≤ x ≤ 1.2, 0.8 ≤ y ≤ 1.2 and 0 ≤ δ ≤ 1.5, Formula 16 What x M y A 3±δ wherein, in Formula 16, M in Formula 16 is at least one element from Group 2 to Group 16, and 0.6 ≤ x ≤ 1.0, 0 ≤ y ≤ 0.4 and 0 ≤ δ ≤ 0.
5.
25. The positive electrode according to claim 24, wherein A is at least one of Sr, Ba, or La, B′ is at least one of Zr, Ce, Sc, Y, In, or Yb, and M is at least one of Sc, Y, Zr, In, La, Pr, Sm, Gd, or Yb.
26. A lithium-air battery, comprising: a positive electrode according to any one of claims 1 - 25; a negative electrode comprising lithium; and an electrolyte disposed between the positive electrode and the negative electrode.
27. The lithium-air battery according to claim 26, wherein the electrolyte is a solid electrolyte.
28. A method for preparing a positive electrode according to any one of claims 1 - 25, the method comprising: providing a composition comprising a metal oxide and a binder; disposing the composition on a substrate; drying the composition on the substrate to prepare a coating; pressing the coating to prepare a sheet; and heat-treating the sheet in an oxidizing atmosphere at a temperature of 450°C to 800°C to prepare the positive electrode.
29. The method for preparing a positive electrode according to claim 28, wherein the method further comprises: Before pressing the coating to prepare a sheet, preparing a stack of coatings, wherein the stack of coatings comprises a plurality of the coatings.
30. The method for preparing a positive electrode according to claim 28, wherein the composition further comprises organic particles having a size of 1 micron or greater.
31. The method for preparing a positive electrode according to claim 30, wherein the amount of the organic particles is 5 parts by weight to 60 parts by weight based on 100 parts by weight of the metal oxide.
32. The method for preparing a positive electrode according to claim 28, wherein the metal oxide comprises a lithium-containing metal oxide.
33. A positive electrode configured to use oxygen as a positive electrode active material, the positive electrode comprising: A porous membrane, wherein the porous membrane comprises a metal oxide, and the metal oxide is a lithium-containing metal oxide represented by Formula 1, Formula 1 Li x A y G z About 3-δ wherein, in Formula 1, each A and G is independently at least one element of Group 2 to Group 16, 0 < x < 1, 0 < y < 1, 0 < x + y ≤ 1, 0 < z ≤ 1.5 and 0 ≤ δ ≤ 1.5, and wherein the surface of the porous membrane has a root mean square roughness of 0.01 micron to 1 micron.
Citation Information
Patent Citations
Cosmetic container with dual type refill container
KR1020200013301A
Gas diffusion electrode base and method for producing gas diffusion electrode base
CN107078308A
Gas diffusion layer for battery, membrane electrode assembly for battery using the gas diffusion layer for battery, member for battery, battery, and method for producing the gas diffusion layer for battery
JP2017050185A
Cited By
Catalyst for catalytic hydrogenation of pyridine, preparation method of catalyst and method for preparing piperidine through catalytic hydrogenation of pyridine
CN121082276A